Layered catalyst article with compartments - Patents.com

By partitioning the levels of different chemical components in the catalyst article and forming multiple catalytic activity competitions, the problem that existing catalyst systems are difficult to remove NOx and other harmful gases under low temperature conditions is solved, and efficient removal and thermal stability are achieved.

JP2025511311APending Publication Date: 2025-04-15DINEX AS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024558322
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-30
Filing Date
2023-03-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

When handling diesel engine emissions, existing catalyst systems are difficult to effectively remove nitrogen oxides (NOx) and other harmful gases, especially under low temperature conditions, and the thermal stability of the catalyst is insufficient after long-term use.

Method used

A catalyst article with a multi-layer structure is used to form multiple catalytic activity components by partitioning the layers of different chemical components in the catalyst article to improve the oxidative activity of NOx, CO and HC and enhance the stability under high temperature conditions.

Benefits of technology

It has achieved efficient removal of NOx and other harmful gases under low temperature conditions, improved the thermal stability and long-term use performance of the catalyst, and met current emission standards and engineering goals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511311000001_ABST
    Figure 2025511311000001_ABST
Patent Text Reader

Abstract

The present disclosure relates to a catalyst article (1) with zones and compartments, which in a preferred embodiment comprises platinum group metal (PGM) elements, such as platinum (Pt) and palladium (Pd), and porous support materials, such as aluminum oxide (Al2O3), silicon oxide (SiO2), titanium oxide (TiO2), and optionally other metal oxides and promoters, that can be used to make a catalyst article (1) with zones for oxidizing carbon monoxide (CO), hydrocarbons (HC), hydrogen (H2), and nitrogen oxides (NOx) emissions, which is further suitable for use as a temporary storage of NOx and hydrocarbons to reduce the total emissions of NOx and hydrocarbons. The present disclosure describes the contents of the catalyst article (1) and how to utilize such a catalyst article (1) in the purification of exhaust gas emissions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a catalyst article (1) with zones and compartments, which in a preferred embodiment comprises platinum group metal (PGM) elements, such as platinum (Pt) and palladium (Pd), and a porous support material, such as aluminum oxide (Al2O3), silicon oxide (SiO2), titanium oxide (TiO2), and optionally other metal oxides and promoters, which are capable of absorbing carbon monoxide (CO), hydrocarbons (HC), hydrogen (H2), and nitrogen oxides (NO x ) can be used to create a catalytic article (1) with a zone for oxidizing NO x and NO to reduce total hydrocarbon emissions. x and further suitable for use as temporary storage of hydrocarbons. The present disclosure describes the contents of the catalyst article (1) and how to utilize such catalyst article (1) in the purification of exhaust gas emissions. [Background technology]

[0002] Although diesel engines operate under lean conditions (λ>1), the exhaust gas emitted from a lean-burn engine contains residual amounts of hydrocarbons (HC) and carbon monoxide (CO). To control the harmfulness of the emissions, these compounds are typically oxidized in a diesel oxidation catalyst (DOC) to less harmful exhaust compounds, such as carbon dioxide (CO2) and water (HO). In addition to these exhaust gas components, nitrogen oxides (NO x ) and particulate matter (PM) emitted from lean-burn engines.

[0003] Due to the demand for lower carbon dioxide (CO) emissions (i.e., lower fuel consumption and temperatures) in light and heavy lean applications, and increasingly stringent emission limits for pollutants set by government authorities, there is a continuing need in the art for improved catalyst systems.

[0004] NOx and particulate matter (PM) are typically removed by exhaust gas aftertreatment units, e.g., NO x is removed by selective catalytic reduction (SCR) with urea and particulate matter (PM) is removed by the diesel particulate filter (DPF), but SCR and the oxidation of PM are aided by nitrogen dioxide (NO2), which can be formed again by the oxidation of nitric oxide (NO) in the diesel oxidation catalyst (DOC).

[0005] In the art, NO x To store NO for a long lean period and periodically reduce the exhaust for a short rich (λ<1) period, e.g., 2-5 seconds, the average lean exhaust is enriched with lean NO. x It is known to apply lean NO storage (LNT). x Storage (LNT) has become more popular in light duty diesel and gasoline applications than in heavy duty diesel applications due to fuel economy and to have a compact system without the use of additional reductant.

[0006] In the art, dilute NO x Combinations of storage (LNT) and selective catalytic reduction (SCR) units have also been introduced, e.g., for lean NO x Excess ammonia (NH3) formed during the enrichment period during storage (LNT) is converted to dilute NO x It is utilized in a selective catalytic reduction (SCR) unit downstream of storage (LNT).

[0007] All NO x In removing waste products, passive NO x The adsorbent (PNA) absorbs NO upstream of the selective catalytic reduction (SCR) catalyst. x The compound is temporarily stored and then the stored NO x The compounds can be released at temperatures favorable for selective catalytic reduction (SCR) reactions, for example temperatures above 200°C.

[0008] Since diesel exhaust gas temperatures are typically in the range of 100-500°C depending on operating conditions, high CO and hydrocarbon (HC) oxidation activity of the catalyst is required to avoid cold start emissions due to insufficient catalyst warm-up.

[0009] Generally, the carbon present in particulate matter (PM) is either passively regenerated in the DPF continuously at low temperatures (<230°C) with NO2 (C+NO2, slow reaction) or actively regenerated (C+O2, fast reaction) by periodic fuel (hydrocarbon) injection and throttling, which raises the temperature up to the carbon oxidation temperature (around 600°C). Depending on the regeneration strategy with the active DPF chosen, a high hydrocarbon concentration in the exhaust gas, e.g. 0.5-2.0% by volume, leads to a high hydrocarbon ignition temperature (T 50 ) rises.

[0010] High hydrocarbon concentrations are known to inhibit the oxidation of CO, hydrocarbons, and NO, resulting in a significant increase in the hydrocarbon light-off temperature by approximately 50-100°C compared to standard diesel exhaust conditions (at <500 ppm hydrocarbons). Therefore, high NO to NO2 oxidation activity at low temperatures (<230°C) is required to enable high performance of selective catalytic reduction (SCR). High CO, hydrocarbon, and NO oxidation activity is required to meet current emission limits and prescribed engineering targets.

[0011] Currently, when diesel engines are running at near maximum power, exhaust gas temperatures typically exceed 400-500°C, especially during active catalyst regeneration. Even now, diesel oxidation catalysts (DOCs) are designed to withstand some degree of uncontrolled particulate matter (PM) oxidation or diesel particulate filter (DPF) regeneration at peak temperatures up to 700-800°C without increased loss of activity, even under controlled DPF regeneration conditions where temperatures should generally not exceed 650°C. Nevertheless, at the highest temperatures, it is essential that the catalyst retains good long-term stability to maintain high catalytic activity over the life of the catalyst.

[0012] Platinum (Pt) is known in the art to have good oxidation activity for CO, hydrocarbons, and NO. However, the thermal durability of Pt is considered to be average compared to other alternatives known in the art. To increase the thermal durability of Pt, palladium (Pd) is often added to diesel exhaust catalysts. Pd is also a commonly used component in diesel oxidation catalysts (DOCs) due to its good activity and selectivity for the oxidation of hydrocarbons and CO.

[0013] Pt and Pd have different catalytic properties for different hydrocarbon types, and their combination is usually considered essential for exhaust gases with saturated / unsaturated and light / heavy hydrocarbons, including oxygenated hydrocarbons. However, Pd is highly susceptible to deactivation in the presence of sulfur. The high cost of platinum group metals (PGMs), especially Pd, makes alternative materials desirable to improve catalyst stability.

[0014] The observation that Pt and Pd have different properties and activity in catalytic reactions under lean conditions led early on to the idea of ​​having zoned catalytic materials in catalysts for internal combustion engines (US3947545, Toyota). Similarly, layered type catalysts are also well known in the art, see for example GB1330842A which details a catalyst comprising a metal oxide in a bottom layer and a platinum group metal and a metal oxide in an upper layer.

[0015] Sulfur compounds in the exhaust gas stream, such as sulfur oxides (SO x It is well known that the presence of sulfur compounds in the aftertreatment system affects the performance of the aftertreatment system. Diesel oxidation catalysts (DOCs) are commonly used as the first catalytic unit in the flow direction in current aftertreatment systems. Sulfur compounds react with the catalytic surface of the diesel oxidation catalyst (DOC), and the catalyst converts harmful exhaust gas components, such as CO, hydrocarbons, and NO, into sulfur compounds. x In addition, sulfur-containing particles may be stored in diesel particulate filters. However, high temperature conditions, typically above 500°C, may cause these stored sulfur compounds to be released from the catalyst.

[0016] Diesel exhaust gas may contain other impurities, such as phosphorus, zinc, or silicon, for example, from lubricants, oils, and / or fuels. Such impurities may also reduce the performance of the catalyst system, and therefore their presence in the aftertreatment system unit should be avoided. In contrast to sulfur, catalyst poisoning by other chemical elements and compounds is usually irreversible, with effects that cannot be restored to the activity of the catalyst.

[0017] Apart from the effects of impurities present in the exhaust gas stream, catalytic activity may also be reduced by exposure of the catalyst system to high exhaust temperature conditions, for example, above 800° C. The negative effects of high temperature conditions, for example in the presence of water, can be partially avoided by utilizing appropriately selected materials known in the art and by improved preparation methods for catalyst manufacture. Also, minimizing exposure time at high temperature conditions reduces catalyst deactivation.

[0018] In the art, aluminum oxide (e.g., Al2O3), silicon oxide (e.g., SiO2), and / or mixtures thereof are well-known porous support materials used in catalysts for lean operation applications. For example, aluminum oxide is well-known as a porous support material to provide high surface area for platinum group metal (PGM) components. Silicon oxide, when used together with aluminum oxide, increases the thermal and chemical stability of the catalyst.

[0019] The purpose of the porous support material in the prior art catalyst articles and in the catalyst article (1) of the present disclosure is to provide a solid matrix for supporting various reaction promoters and to allow high surface area for the desired contact of gas molecules to undergo various catalytically improved reactions desired in the field of the present invention. In the field and herein, such solid matrices for supporting reaction promoters are referred to as supports, and materials capable of forming supports are referred to as support materials, respectively. These terms are used similarly herein.

[0020] In the art, for example, Si oxide (e.g., EP0377290), Ti oxide (e.g., JP4087627), Si-Ti oxide (e.g., US5,145,825) and / or Zr oxide supports are known to be used to provide catalysts, which are less likely to adsorb sulfates and have been applied to catalysts to improve sulfur tolerance in diesel oxidation catalysts (DOC). The effects of various substitutes, such as Sc, Ti, Cr, Mn, Fe, Co, Cu, La, Au, Ag, Ga, In, Ce, V, Mo, W, Zr, Nb, Pr, and zeolites as reaction promoters in different roles have also been proposed in the prior art (see, for example, WO2004091782).

[0021] Various accelerants can be tailored to the PGM component or by particle size. For example, the PGM component can be tailored to zeolite or ceria. Aluminum (Al) and cerium (Ce) oxides can be added to SO x It has been shown that when used for adsorption, sulfur-containing species can be decomposed at moderate temperatures. For example, when lanthanum (La), barium (Ba) and yttrium (Y) components are used, more stable sulfates are produced by catalysis, see for example WO1993022050A1. Similarly, aluminum and cerium oxides have been applied to zeolites since the 1990s in Pt-DOC, see for example WO9401926. Tungsten (W) is also used in the art for emission catalysts in selective catalytic reduction (SCR) (VW / TiO2) and TWC, see for example EP0056729.

[0022] Additionally, many different types of accelerants and PGM loadings / ratios have been proposed in the art for DOC, especially as single compositions. However, many additives are accelerants for certain properties, but have no or even negative effects on other properties. For example, the best composition for ignition of hydrocarbons requires very little NO oxidation, and similarly, the best catalyst for NO oxidation may have limitations in the oxidation of hydrocarbons and CO. Additionally, local PGM distribution / dispersion and mass / heat transfer play an important role in the catalytic reaction chain and durability. Summary of the Invention [Problem to be solved by the invention]

[0023] Given the aforementioned complexities in catalyst design, stringent exhaust gas legislation necessitates the development of improved performance and cost-effective oxidation and lean catalysts and aftertreatment systems (ATS). To enable this, the availability of PGM components and associated support material components becomes much more important to ensure good performance and long term durability. [Means for solving the problem]

[0024] The catalyst article (1) of the present disclosure performs the catalytic reactions included in catalytic aftertreatment systems (ATS) for purifying and oxidizing exhaust gas emissions from lean internal combustion engine operating conditions. The catalyst article (1) of the present disclosure is responsible for the oxidation and removal of carbon monoxide (CO), hydrocarbons (HC), hydrogen (H2), and the oxidation of nitric oxide (NO) to nitrogen dioxide (NO2), as well as the reduction of nitrogen oxides (NO) in such aftertreatment systems. x ) is used to enhance removal efficiency.

[0025] The catalytic article (1) of the present disclosure also includes NO x The total NO2 is measured after the ATS flow path by temporarily storing the emissions. x NO emissions can be reduced xThese catalytic functions performed by multiple layers and zones according to the present disclosure can be applied in the same catalytic article (1).

[0026] Definitions and Abbreviations λ lambda, fuel-air equivalence ratio Gamma ASC - Ammonia Slip Catalyst ATS - Aftertreatment System BET - Brunauer-Emmett-Teller method for specific surface area calculation. CEO x - cerium oxide(s) cpsi - cells per square inch deNO x - Removal of nitrogen oxides DOC - Diesel Oxidation Catalyst DPF - Diesel Particulate Filter Effective Total Active Metals per Volume: PGM, ingredient or coating loading in g / L, i.e. grams of PGM, ingredient or coating per liter of total substrate volume. Volumetric PGM loading is meaningful to understand total PGM added (effective total active metals per volume) without knowing the exact substrate geometric area, coating density. HC - Hydrocarbon(s) HT - Hot water HT700 - 700℃ hot water (aging) In-B - Bottom of inlet, proximal to inlet In-T - Inlet upper, inlet distal LaO x - Lanthanum oxide(s) LNT - Lean NO x Storage NO x - Nitrogen oxide(s) Out-B- At the bottom of the outlet, near the outlet Out-T - Upper outlet, distal outlet PNA - Passive NO x Adsorbent PGM - Platinum Group Metals SAR - Si / Al2 ratio, molar SCR - Selective Catalytic Reduction SGB ​​- Synthetic Gas Bench SO x - Sulfur oxide(s) SV - space velocity T 50 Ignition temperature, the temperature at which 50% conversion is achieved TWC - Three-way catalyst WHTC - World Harmonized Transient Cycle WO x - Tungsten oxide(s) ZrO x - zirconium oxide(s)

[0027] Figures 1-7 are illustrations of exemplary embodiments of the catalyst article (1) of the present disclosure and the prior art. Figures 8-17 show experimental evidence of the technical benefits of the present disclosure. [Brief description of the drawings]

[0028] [Figure 1] FIG. 1 shows a catalyst article (1) of the present disclosure including adjacent, overlapping inlet bottom (In-B) coating layer, outlet bottom (Out-B) coating layer, inlet top (In-T) coating layer, and outlet top (Out-T) coating layer. [Figure TRB] FIG. TRB shows a catalytic article (1) of the present disclosure, comprising an inlet bottom (In-B), an outlet bottom (Out-B), an inlet top (In-T) and an outlet top (Out-T) coating layer, adjacent and overlapping each other, with varying coating lengths and thicknesses. As detailed in the figure, the overlapping top and bottom layers form an intermediate section according to FIG. 5. In the example of FIG. TRB, In-T overlaps Out-B, thereby forming an intermediate section, although the reverse is equally possible, Out-T overlapping In-B, but is not shown here. [Diagram 3] FIG. 1 shows a prior art catalytic article (1) including an inlet bottom (In-B) coating layer, an outlet bottom (Out-B) coating layer identical to the In-B coating layer, an inlet top (In-T) coating layer, and an outlet top (Out-T) coating layer adjacent to and overlapping each other. In the art, such catalytic articles (1) are produced by first coating the bottom layer (in the terminology of the figure, both In-B and Out-B are coated simultaneously) and then adding two different top coatings, In-T and Out-T. In the present disclosure, the prepared sample having the coating structure according to FIG. 3 is an exemplary teaching for use according to the teachings of the present disclosure, as detailed in Example 12 and FIG. 17. [Diagram 2] 1 shows a prior art catalyst article (1) comprising an inlet bottom (In-B) coating layer, an outlet bottom (Out-B) coating layer identical to the In-B coating layer, an inlet top (In-T) coating layer, and an outlet top (Out-T) coating layer identical to the In-T coating layer, which are stacked on top of each other. The present disclosure relates to a catalyst article (1) carrying at least two compartments, characterized in that the at least two compartments comprise at least two chemically distinct layers (In-B, In-T or Out-B, Out-T), and in that at least the inlet bottom layer is chemically or morphologically distinct from the outlet bottom layer, and in that the inlet bottom layer is chemically or morphologically distinct from the outlet bottom layer. [Diagram 5] FIG. 1 illustrates a catalyst article (1) of the present disclosure including three sections, namely an inlet section, a middle section, and an outlet section, created by adjacent and overlapping inlet bottom (In-B) coating layer, a middle bottom (Mid-B) coating layer, an outlet bottom (Out-B) coating layer, an inlet top (In-T) coating layer, a middle top (Mid-T) coating layer, and an outlet top (Out-T) coating layer. [Figure 6]FIG. 1 shows a catalyst article (1) of the present disclosure including three sections, namely an inlet section, a middle section, and an outlet section, created by adjacent and overlapping inlet bottom (In-B) coating layer, outlet bottom (Out-B) coating layer, a middle (Mid) coating layer, an inlet top (In-T) coating layer, and an outlet top (Out-T) coating layer. [Figure 7] FIG. 1 shows a catalyst article (1) of the present disclosure including adjacent, overlapping inlet bottom (In-B) coating layer, outlet bottom (Out-B) coating layer, inlet top (In-T) coating layer, outlet top (Out-T) coating layer and second top (2nd top) coating layer. [Figure 8] 1 is a graph showing the difference in NO to NO2 oxidation (%) measured after a layered catalyst article (1) containing W+Pt (Example 1), a single layer coating composition containing W+Pt (Example 2), and a single layer REF (Example 3) in a steady-state experiment in a diesel engine. [Figure 9] 1 is a graph showing the difference in NO to NO2 oxidation (%) measured after HT700 aging of banded / layered samples with Pt+Pd+W (Example 4), layered samples with Pt+W (Example 5), and layered samples with Pt+Pd (Example 6) in SGB testing. [Figure 10] 1 is a graph showing the difference in CO and THC light-off temperatures (° C., T50) measured at standard and regenerated conditions after HT700 aging of banded / layered samples with Pt+Pd+W (Example 4), layered samples with Pt+W (Example 5), and layered samples with Pt+Pd (Example 6) in SGB testing. [Figure 11] 1 is a graph showing the difference in NO to NO2 oxidation (%) measured after HT700 aging of Pt+Pd+W containing banded / layered sample (Example 7) and Pt+Pd containing banded / layered sample (Example 8) in SGB testing. [Figure 12]1 is a graph showing the difference in NO to NO2 oxidation (%) measured after HT700+SO2 aging of Pt+Pd+W containing banded / layered sample (Example 7) and Pt+Pd containing banded / layered sample (Example 8) in SGB testing. [Figure 13] 1 is a graph showing the difference in THC ignition temperature (° C., T50) measured at standard conditions across HT700 and HT700+SO2 aged Pt+Pd+W containing zoned / layered samples (Example 7) and Pt+Pd containing zoned / layered samples (Example 8) in SGB testing. [Figure 14] 1 is a graph showing the difference in NO to NO2 oxidation (%) measured after HT700 aging of a banded / layered sample containing Pt+Pd+W (Example 9) and a banded / layered sample containing Pt+Pd (Example 10) in an SGB test. [Figure 15] 1 is a graph showing the difference in CO and THC ignition temperatures (° C., T50) measured at standard conditions across HT700 aged Pt+Pd+W containing zoned / layered samples (Example 9) and Pt+Pd containing zoned / layered samples (Example 10) in SGB testing. [Figure 16] FIG. 1 is a graph showing the relative desorbed NOx (%) from fresh layered samples (Examples 11a-g) as a function of temperature. [Figure 17] 1 is a graph showing the difference in NO to NO2 oxidation (%) measured for the catalytic article with compartments (1) in an SGB test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] It should be understood that the embodiments shown in the figures are for the purpose of illustrating the invention and are not to be construed as limiting the invention. Unless otherwise specified, the figures are intended to be read together with the specification (e.g., cross-hatching, arrangement of parts, proportion, degree, etc.) and should be considered part of the entire written description of the present disclosure.

[0030] As detailed hereinabove, layered catalyst articles are commonly used in the art, and typically employ two layers having different chemistries for the purpose of promoting one or more conversion reactions across the length of the catalyst article.

[0031] In a layered catalyst article, a layer is brought into contact with the surface of an underlying substrate (2) to form a proximal coating layer on the underlying substrate, and additional distal layers are successively formed on top of each underlying coating layer, resulting in the layer being closer to the underlying substrate. This principle is illustrated in Figures 2 and 3, and is partially shown in Figure 1C, as viewed along the direction of gas flow through the catalyst article.

[0032] In order to maintain gas flow throughout the catalyst article (1), there is a limit to how much gas passage across the catalyst article can be reduced by the addition of additional catalyst coating layers before the pressure drop across the catalyst article becomes a limiting factor to the normal operation of the vehicle in which the catalyst article is installed.

[0033] At the same time, the available volume in an engine assembly that can be allocated to catalyst articles for exhaust gas conversion is limited by engine assembly design constraints, so catalyst performance cannot be improved by simply changing the dimensions of catalyst articles known in the prior art.

[0034] Therefore, optimization of catalytic conversion across the catalyst article is of paramount importance.

[0035] The present disclosure, in a first aspect and embodiment, relates to a layered (or zoned) and sectioned catalyst article (1) in which, by appropriate selection of catalytically active components in the catalyst layers, the catalyst article (1) is created having at least two catalyst sections (10, 20, 30), each catalyst section being selective for catalytic conversion of one or more chemical exhaust components contained in exhaust gases from a fueled internal combustion or explosion engine to one or more desirable emission components.

[0036] Surprisingly, the inventors have discovered that by selectively dividing a catalytic article for exhaust gas conversion into smaller catalytically active sections, where a given section is catalytically active towards a different exhaust gas component compared to the remaining catalytically active sections, an overall improvement in exhaust gas conversion can be realized with only a slight, if any, decrease in the exhaust quality of individual undesirable gas components of the exhaust gas.

[0037] In this disclosure, the principles of the present invention are discussed in the context of a catalyst article (1) including two catalyst sections (10, 20), where a first catalyst section (10) is selective for converting hydrocarbons (HC), H2, or carbon monoxide (CO) from the exhaust gas to water and carbon dioxide, and a second catalyst section (20) is selective for converting nitric oxide to nitrogen dioxide and / or sulfur monoxide to sulfur dioxide.

[0038] By selectively removing hydrocarbons, hydrogen and / or carbon monoxide below critical levels for contamination of the second compartment, operation of the NOx / SOx oxidation catalyst can be maintained operatively, thereby optimizing the total catalyst volume across the catalyst article of the present invention.

[0039] Accordingly, in a first aspect and embodiment herein, there is provided a catalytic article (1) for purifying exhaust gas at lean exhaust gas conditions, the catalytic article (1) comprising flow paths (3) for allowing exhaust gas to traverse the catalytic article (1), thereby defining inlets and outlets for the exhaust gas and a flow direction of the flow paths for the exhaust gas traversing the catalytic article (1), the flow paths (3) providing a surface of a substrate (2) for carrying one or more catalytically active layers (11, 12, 21, 22) for converting at least a respective first and a respective second undesirable chemical component contained in the exhaust gas into at least a corresponding first or corresponding second desired chemical component during the passage of the exhaust gas through the catalytic article (1); - at least first and second catalyst sections (10, 20) are arranged on the substrate (2), each catalyst section (10, 20) comprising at least a respective first and a respective second catalyst layer (11, 12), (21, 22) arranged such that the respective first catalyst layer (11, 21) is proximal to the substrate (2) and the respective second catalyst layer (12, 22) is distal to the substrate (2); - each of the first and second catalyst layers (11, 12, 21, 22) is chemically different from the other; - a first catalyst section (10) is disposed in the flow path (3) such that the exhaust gas, while traversing the flow path (3), first encounters the first catalyst section (10) and then encounters the second catalyst section (20); - the second catalytic section (20) promotes, and the first catalytic section (10) does not substantially promote, the catalytic conversion of either the first or second undesired chemical constituent into the corresponding first or second desired chemical constituent; A catalytic article (1) is described in detail.

[0040] The general configuration of the catalyst article (1) according to the present invention is detailed in Figure 1. The catalyst article (1) of the present disclosure provides a surface of a substrate (2) where, at the inlet and outlet defined by the flow direction, two sections (10, 20) respectively start at the inlet (first section) and end at the outlet (second section) to create a desired coating composition present on the surface of the substrate (2). The sections may start and end at different positions from the inlet and outlet due to the spatial optimization of the catalyst article (1), but in practice they will never do so.

[0041] To simplify the present text, the first proximal coating (11) is labeled and discussed as In-B, the first distal coating (12) is labeled and discussed as In-T, the second proximal coating (21) is labeled and discussed as Out-B, and the second distal coating (22) is labeled and discussed as Out-T. As a result, the distal (top) coating layer of the inlet and outlet adheres to the proximal (bottom) coating layer of the inlet and outlet. Thus, the bottom and top coating layers described herein are defined relative to the surface of the substrate (2), not by gravitational measurement, but by the bottom being most proximal to the surface of the substrate (2) and the top being most distal to the surface of the substrate (2).

[0042] The substrate (2) typically forms a honeycomb structure and flow channels to provide low pressure drop and a large geometric surface for the thin catalyst coating layer. The surfaces of the substrate (2) lie within the walls and pores of the substrate (2) and form its internal flow channels, or flow passages (3) in claim terminology.

[0043] As discussed above and shown in Figures 2 and 3, it is known in the art to make zoned catalyst articles. The catalyst article shown in Figure 2 is a typical bi-layered catalyst article in which the top and bottom coatings are identical throughout the length of the catalyst article, and therefore does not provide a zoned catalyst.

[0044] In contrast, the catalyst article of FIG. 3 has a first and a second catalytic zone because the two upper catalyst layers are chemically different. However, in the art, the bottom layer (proximal layer in the terms of the claims) remains uniform. Generally, in this configuration, the catalyst article cannot perform more than one catalytic function across the catalyst article, but it does allow for improved catalytic conversion by increasing the content of an otherwise expensive catalyst promoter, such as platinum or palladium, in the second upper layer located towards the outlet of the catalyst article, for example, while the content of catalytic reactant can be kept at a lower level in the first zone, since it is higher at the inlet of the exhaust gas to the catalyst article.

[0045] In the catalytic article (1) of the present invention, this principle is omitted by having all four catalytic layers chemically different from each other, thereby realizing a true catalytic partition into at least two different catalytic compartments, such that a first catalytic compartment (10) is capable of promoting a first catalytic conversion and a second catalytic compartment (20) is capable of promoting a different catalytic conversion that is not substantially promoted by the first catalytic compartment (10).

[0046] In the context of the present application, a catalytic section is considered not to substantially promote a catalytic reaction if not more than that, preferably not more than that, 15% or preferably not more than that, of a particular chemical component is converted as a by-product in a catalytic section otherwise arranged to convert a different chemical component.

[0047] In a preferred embodiment of the present invention, where the first catalyst section (10) is arranged to convert hydrocarbons, H2, and CO to water and CO2, and the second catalyst section (20) is arranged to convert NOx and / or SOx to NO2 and / or SO3, the conversion of NOx and / or SOx to NO2 and / or SO3 occurs in the second catalyst section (20), substantially only in the second catalyst section (20), affecting the conversion of the first catalyst section (10) (see Experimental). Thus, the separation of the two catalytic processes has been successfully achieved by the created sections.

[0048] In a preferred embodiment, the first catalyst section (10) achieves sufficient completion of HC, H2, and CO conversion so that NOx / SOx conversion in the second catalyst section (20) can occur without catalyst poisoning. However, as shown by experiments, the devised second catalyst section (20) also succeeds in a second conversion of at least some of the unreacted HC, H2, and CO remaining in the exhaust gas, which is beneficial. Thus, in the present invention, there is no strong limit on the catalytic effect of the second catalyst section (20) relative to the first catalyst section (10), but there is a limit with respect to the first catalyst section (10) in order to be able to use the second catalyst section (20) with maximum efficiency.

[0049] The figure further shows various lengths indicating the length of the catalyst article (1) and the thickness of the various catalyst layers (11, 12, 21, 22). As will be explained in more detail herein below, in some embodiments, variation in layer size (effectively layer volume) forms part of the modification of the catalyst layers to obtain the maximum effect of the catalyst compartmentalization of the present invention.

[0050] In some embodiments of the catalyst article (1) according to the present disclosure, as detailed in Figures 4-6, at least a third section (30) is disposed in the flow path (3) after the first catalyst section (10) and before the second catalyst section (20) in the flow direction of the exhaust gas through the flow path (3).

[0051] 4 details an embodiment in which the third compartment (30) is created by overlapping the first distal catalyst layer (12) with the second proximal catalyst layer (21), i.e., the overlapping of the In-T and Out-B layers. The effect of this overlap is generally to avoid diffusion loopholes due to poorly bonded coating layers, and in a preferred embodiment of the invention, this overlapping further allows the storage of reactants in the second proximal catalyst layer (21) to improve the catalytic conversion in the second catalyst compartment (20), even if the HC, H2, and / or CO conversion occurring in the first distal catalyst layer (12) is not yet completed.

[0052] The embodiment detailed in FIG. 4 is particularly preferred from the standpoint of ease of manufacture and for catalytic conversion, as discussed above, although a third compartment (30), if this is involved, can obviously also be created by overlapping a second, distal catalyst layer (22) with a first, proximal catalyst layer (11).

[0053] 5 and 6 show a further embodiment of a third section (30) that may be useful in certain circumstances in the catalyst article (1) of the present invention.

[0054] FIG. 5 details an embodiment in which the third compartment (30) is intended to be a third catalyst compartment (30) having a third proximal catalyst layer and a third distal catalyst layer having a chemistry and reaction volume adapted to carry out a third catalytic conversion not carried out by either the first (10) or second (20) catalyst compartments.

[0055] In figure 6 an embodiment is detailed in which the third section (30) is a single layer connecting the first and second catalyst sections (10, 20) described above. In some embodiments, for example for manufacturing purposes, it may be beneficial to have a neutral zone between the two catalyst sections, and this is reflected in the embodiment shown.

[0056] As detailed above, in the most preferred embodiment of the catalyst article (1) of the present invention, the first catalyst section (10) is selective for converting hydrocarbons, H2, and / or carbon monoxide (CO) from the exhaust gas to water and carbon dioxide, and the second catalyst section (20) is selective for converting nitric oxide to nitrogen dioxide and / or sulfur dioxide to sulfur trioxide.

[0057] According to the most preferred embodiment, in one embodiment, the first catalyst section (10) comprises in the first proximal catalyst layer (11) one or more catalytically active metals selected from the platinum group metals (PGM) including Pt, Pd, Rh, Ir, Ru, Os in a loading of less than 0.8 g / L and in the first distal catalyst layer (12) one or more catalytically active metals selected from the platinum group metals (PGM) including Pt, Pd, Rh, Ir, Ru, Os in a loading of between 0.5 and 7.0 g / L, with the proviso that the metal loading in the first distal catalyst layer (12) is greater than the metal loading in the first proximal catalyst layer (11).

[0058] According to the most preferred embodiment, in one embodiment, the platinum group metals selected for the first proximal (11) and distal (12) catalytic layers are platinum and / or palladium.

[0059] According to the most preferred embodiment, in one embodiment, platinum and palladium are present in the first distal catalytic layer (12) in a Pt:Pd ratio ranging from 1:4 to 5:1, and in the first proximal catalytic layer (11) in a Pt:Pd ratio ranging from 1:9 to 9:1.

[0060] According to a most preferred embodiment, in one embodiment, the second catalyst section (20) of the second proximal catalyst layer (21) comprises one or more catalytically active metals selected from the platinum group metals (PGM) including Pt, Pd, Rh, Ir, Ru, Os at a metal loading of less than 0.8 g / L and the second catalyst section (20) of the second distal catalyst layer (22) comprises one or more catalytically active metals selected from the platinum group metals (PGM) including Pt, Pd, Rh, Ir, Ru, Os at a metal loading of between 0.1-2.0 g / L, with the proviso that the metal loading in the second distal catalyst layer (22) is greater than the metal loading in the second proximal catalyst layer (21), and the second distal catalyst layer (22) further comprises tungsten (W) and / or molybdenum (Mo) in an amount sufficient to promote conversion of NOx to nitrogen dioxide.

[0061] According to the most preferred embodiment, in one embodiment, the platinum group metals selected for the second proximal (21) and distal (22) catalytic layers are platinum and / or palladium.

[0062] According to the most preferred embodiment, in one embodiment, the Pt:Pd ratio in the second distal catalyst layer (22) is in the range of 1:0 to 30:1, and the Pt:Pd ratio in the second proximal catalyst layer (21) is in the range of 1:9 to 9:1.

[0063] According to a most preferred embodiment, in one embodiment, tungsten (W) is present in the second distal catalyst layer (22) as tungsten oxide (WO3) in the range of 1-30 g / L.

[0064] According to the most preferred embodiment, in one embodiment, the PGM loading in the catalyst coating layer follows the order In-T≧Out-T>In-B>Out-B, but preferably follows the order In-T>Out-T>In-B>Out-B.

[0065] According to a most preferred embodiment, in one embodiment, the first (11) and second (21) proximal catalyst layers are x The catalyst further comprises a sufficient amount of cerium (Ce) oxide or a mixed cerium oxide selected from ZrCe, MnCe, TiCe, PrCe oxide, or a combination thereof, to promote adsorption-desorption and NO2 formation by desorption at less than 200°C.

[0066] According to the most preferred embodiment, in one embodiment, cerium in the form of cerium oxide or cerium mixed oxide is present in an amount of 0.05 g / L to 0.5 g / L based on the total weight of the cerium oxide or cerium mixed oxide.

[0067] According to a most preferred embodiment, in one embodiment, the first (11) and second (21) proximal catalyst layers are the NO 3 of the first and second proximal catalyst layers. x and S.O. xTo enhance the adsorption capacity, it further comprises lanthanum (La), yttrium (Y), hafnium (Hf), or combinations thereof, but preferably lanthanum, as a stable oxide in an amount ranging from 1 to 10 g / L, preferably 3 to 6 g / L.

[0068] According to a most preferred embodiment, in one embodiment, the first (11) and second (21) proximal catalyst layers are x To increase the adsorption capacity, it further comprises one or more zeolites with high Si / Al2 ratio (SAR) selected from Beta, ZSM-5, Chabazite (CHA), AEI, Ferrierite (Fer), Y or combinations thereof in an amount of 5-1000 g / L, but preferably 10-50 g / L.

[0069] According to the most preferred embodiment, in one embodiment, the catalyst layers (11, 12, 21, 22) contain, in addition to the catalytic promoter, aluminum oxide, alumina (Al2O3), silicon oxide (SiO x ), silica (SiO2), titanium oxide (TiO x The porous support includes a porous metal oxide selected from porous metal oxides including titanium dioxide (TiO2), titania (TiO2), or mixtures thereof.

[0070] According to the most preferred embodiment, in one embodiment, the amount of coating in each coating layer is 10-200 g / L, preferably 40-100 g / L, more preferably 50-80 g / L in all layers of the catalyst article (1), with the porous metal oxide forming the remainder of the coating composition.

[0071] In some embodiments, the coating layer comprises porous Al, Si and / or Ti oxides as supports of active compounds and promoters for diffusion exchange with the exhaust gas traversing the catalytic coating layer to bring the exhaust gas into contact with the catalytic coating layer.

[0072] In the present invention, the coating layers have their specific role to enable the high performance of the catalyst article (1) of the present disclosure. In some embodiments, the high performance is based on the composition of each layer and zone with different platinum group metal (PGM) loadings, Pt:Pd ratios, support compositions and promoters added in the flow direction.

[0073] In a preferred embodiment, the radial location (bottom, i.e. proximal; top, i.e. distal) and axial location (inlet, middle, outlet) of the active compounds (PGMs) and promoters in the different coating layers have a very important effect on the functionality and durability to avoid deactivation. In a preferred embodiment of the present invention, the front (inlet) portion of the catalyst article (1) of the present disclosure is mainly involved in the initiation of the reaction and the oxidation of hydrocarbons, H2 and CO.

[0074] During diesel particulate filter (DPF) regeneration, the hydrocarbon compounds with the lowest ignition temperatures, such as unsaturated hydrocarbons with medium carbon chain lengths or aromatic hydrocarbons, are rapidly oxidized in the front section.

[0075] Also, during DPF regeneration, the hydrocarbon compounds with the highest light-off temperatures, e.g., saturated hydrocarbons with significantly short or long carbon chain lengths, require longer residence times, higher reaction temperatures and Pt-rich PGM compositions and are therefore oxidized in the rear (outlet) portion of the catalyst article (1).

[0076] As a result, in a preferred embodiment of the present invention, the entire axial and radial length of the catalyst article (1) of the present disclosure is utilized for the low temperature oxidation of various types of hydrocarbon compounds.

[0077] In a preferred embodiment of the present invention, the rear portion of the catalytic article (1) of the present disclosure is also particularly involved in the oxidation of NO to NO2, thereby oxidizing soot in a particulate filter (e.g., DPF), as well as ammonia or urea (NH3- or urea-SCR) or lean NO x NO in selective catalytic reduction with storage (LNT) units x The return is improved.

[0078] In some embodiments, the catalyst article (1) of the present disclosure has NO as a regulated structure. x By utilizing the adsorption and storage functionality, NO in the complete ATS x It may also include properties to enhance removal efficiency. x The storage function may be applied in the same layer as the layer in which the oxidation reaction takes place, or preferably in a different layer.

[0079] The oxidation and adsorption functions can also be divided into two different catalytic articles (1) of the present disclosure having a specific cell density on a substrate (2).

[0080] Certain metal oxide or zeolite compounds can be used as promoters to improve the performance of the catalyst articles (1) of the present disclosure. These compounds are added to specific locations of the catalyst articles (1) of the present disclosure to optimize their promotion.

[0081] In a preferred embodiment, tungsten (W) in the form of tungsten oxide, e.g., tungsten trioxide (WO), can be utilized to stabilize Pt and improve the activity of the catalytic article (1) of the present disclosure in oxidizing NO to NO. Tungsten (W) is a relatively inexpensive material compared to PGM components, e.g., Pt and Pd, and is therefore a good substitute for them.

[0082] In a preferred embodiment, silicon (Si) and / or zirconium (Zr) compounds in oxide form, such as silica (SiO2) and zirconia (ZrO2), are used to inhibit the addition of sulfur oxides (SO2) to the catalyst article (1) of the present disclosure. x ) adsorption and thus improving the activity and stability over the life of the catalyst article (1) of the present disclosure.

[0083] In a preferred embodiment, lanthanum (La), hafnium (Hf), yttrium (Y), and / or cerium (Ce) compounds in the form of oxides, such as lanthana (La2O3), yttria (Y2O5), and / or ceria (e.g., CeO2), are used to enhance the transport of nitrogen oxides (NO2) to the catalytic article (1) of the present disclosure. x ) adsorption and therefore the overall NO of the ATS. x can be used to reduce emissions.

[0084] In a preferred embodiment, the zeolite is added to the conditioned layer of the catalyst article (1) to form a hydrocarbon or NO x Used as a storage agent to reduce the amount of hydrocarbons and NOx during cold engine start x Reduce emissions.

[0085] The catalytic article (1) of the present disclosure in a preferred embodiment, in which the first catalytic section (10) is selective for converting hydrocarbons (HC), H2, or carbon monoxide (CO) from the exhaust gas into water and carbon dioxide, comprises at least two coating layers having a specific function in removing exhaust gas components.

[0086] In a preferred embodiment, platinum group metal (PGM) components in metallic or oxide form, such as platinum (Pt), palladium (Pd), rhodium (Rh), iridium (Ir), ruthenium (Ru), osmium (Os), and / or precious metals, such as silver (Ag) and gold (Au), but preferably all or most of the PGM components, more preferably Pt and Pd, are present in the top layer according to the main aspects and embodiments of the present invention. In contrast, the bottom coating layer, according to the main aspects and embodiments, has a lower amount of PGMs compared to the top layer or is free of PGM components.

[0087] The PGM loading (g / L, grams of PGM per liter of substrate volume) and Pt:Pd ratio (mass ratio of Pt and Pd) are varied over the length of the catalyst article (1). The amount of PGM component in the front (inlet) portion of the catalyst article (1) may be the same as or greater than the amount of PGM component in the rear (outlet) portion of the catalyst article (1). In contrast, the Pt:Pd ratio in the outlet portion of the catalyst article (1) is the same as or greater than the Pt:Pd ratio in the inlet portion of the catalyst article (1).

[0088] The PGM loading in the catalyst article (1) is primarily defined as a volumetric measurement (grams of PGM per liter of substrate volume, g / L). It is possible to define the PGM loading throughout the front and rear portions of the catalyst article (1) as grams of PGM per volume of the front (or rear) portion of the substrate, but this is not very useful.

[0089] For example, as shown in FIG. 1, the front portion of the catalyst article (1) includes at least two distinct coating layers, namely, inlet-bottom (In-B) and inlet-top (In-T), and the rear portion of the catalyst article (1) includes at least two distinct coating layers, namely, outlet-bottom (Out-B) and outlet-top (Out-T).

[0090] It is also possible to define separate PGM loadings for the top (distal) and bottom (proximal) layers at each location. The PGM loading in the In-T coating layer of the catalyst article (1) (see Figures 1-7) ranges from about 0.5-7.0 g / L, preferably 0.5-3.0 g / L, more preferably 0.8-1.5 g / L, while the Pt:Pd ratio in the In-T coating layer of the catalyst article (1) ranges from about 1:4-5:1, preferably 1:1-4:1, but more preferably 2:1-3:1.

[0091] Both Pt and Pd in ​​the In-T coating layer have low ignition temperatures (T 50It is important to have a high conversion rate (temperature at which 50% conversion is achieved) and to achieve good stability against thermal and hydrothermal aging. Pt and Pd stabilize each other through their close interaction, making bimetallic Pt+Pd catalysts better than single PGM catalysts.

[0092] The PGM loading in the Out-T coating layer of the catalyst article (1) ranges from about 0.1 to 2.0 g / L, preferably 0.3 to 1.5 g / L, more preferably 0.5 to 1.2 g / L, while the Pt:Pd ratio in the Out-T coating layer of the catalyst article (1) ranges from about 3:1 to 30:1, preferably 4:1 to 15:1, more preferably 5:1 to 10:1. In some embodiments, palladium is not even present.

[0093] The high Pt loading in the rear section ensures high activity and durability in the NO to NO2 oxidation reaction. Optionally, the rear section of the catalyst article (1) may also be Pd-free. The PGM loading in the Out-T coating layer is about the same as, or preferably lower than, the PGM loading in the In-T coating layer, and the Pt:Pd ratio is about the same as, or preferably higher than, the Pt:Pd ratio in the In-T coating layer.

[0094] The catalyst article (1) includes at least In-B and Out-B coating layers beneath an upper layer containing PGMs, which can fill the corners of the square channels. The corner filling creates more circular flow channels, which have a relatively lower pressure drop than a square channel of the same hydraulic diameter.

[0095] When the bottom layer contains at least one PGM, exhaust gas components, such as hydrocarbons, CO and NO, diffuse through the top layer. x reaches the active sites in the bottom layer. If most of the PGMs are used in the top coating layer, the mass transfer will be more rapid if the exhaust gas components come into contact with the active sites (PGMs) more quickly. Thus, all or most of the PGMs are located in the top layer.

[0096] In the four-layer structure of the present disclosure, the PGM loadings in the coating layers follow the order In-T≧Out-T>In-B≧Out-B, preferably In-T>Out-T>In-B≧Out-B. While the total loadings of Pt and Pd in ​​some of the layers can be equal, instead, the Pt:Pd ratios are varied to maintain chemical differences among the four layers (In-T, In-B, Out-T, Out-B) as defined by the preferred embodiment of the present invention.

[0097] The composition of the support to which the PGM and promoters are added may be porous metal oxides, such as aluminum oxides, e.g., alumina (Al2O3), silicon oxides (SiO x ), such as silica (SiO2), titanium dioxide (TiO x ), for example titania (TiO2) or mixtures and compounds thereof. Possible promoters are defined separately for each layer. In the main example, the main support material is alumina, preferably in gamma form, which has a high surface area that facilitates the distribution of the active metals and promoters.

[0098] Silica and titania can be added in a controlled manner to different layers to stabilize the PGMs and alumina and to promote certain reactions. When present, TiO2 and SiO2 are preferably present in the top layers (e.g., In-T and Out-T). TiO x and SiO x It stabilizes aluminum oxide, improves sulfur durability, and promotes oxidation reactions on PGMs. In addition, TiO x is preferably present in the inlet layer, and SiO x When present in the outlet layer, Ti oxide can reduce sulfur accumulation and increase sulfur recovery, thereby allowing better sulfur regeneration of the catalyst article (1) when used under regeneration (DPF, desulfation) conditions. Si oxide is preferably present in the outlet layer because Si oxide, together with alumina, can have a promoting effect on NO2 formation over Pt-rich compositions.

[0099] The amount of coating in each coating layer ranges from about 10 to 200 g / L, preferably about 40 to 100 g / L, more preferably about 50 to 80 g / L in all layers of the catalyst article (1). The total amount of coating in the front and rear sections is defined by the amount of coating in In-B+In-T and Out-B+Out-T in the four coating layers, respectively.

[0100] In addition to the alumina and PGM components, any coating layer of the present disclosure may contain other components, such as tungsten oxide (WO x ) and molybdenum oxide (MoO x ), preferably WO x may also be optionally included to improve the activity of the catalyst article (1) and its resistance to impurities. In particular, in a preferred embodiment, WO x For example, WO3 acts to promote NO2 formation in the Pt-rich Out-T coating layer, making its addition favorable.

[0101] The amount of tungsten oxide as WO3, if used, ranges from about 1 to 30 g / L, preferably 3 to 10 g / L, in the portion of the catalyst article (1). x The amount of when present as WO3 in the layer varies from 1 to 20 wt%.

[0102] Zirconium oxide, such as zirconia (ZrO2), may also be used to increase the stability of the catalyst article (1) and its resistance to sulfur oxides and to increase NO2 formation. Zirconium increases the acidity and therefore the SO2 oxidation to alumina-based support materials. xReduces adsorption. Zr can be present in all layers, but is preferably present in the Out-T coating layer to promote and also stabilize NO2 formation in the Pt-rich outlet portion. The total amount of ZrO2, if used, ranges from about 1 to 30 g / L, preferably 3 to 10 g / L, in the catalyst article (1) component. The amount of ZrO2 in the dry coating, if present, varies from 1 to 20 wt% in the layer.

[0103] Lanthanum oxide, such as lanthana (La2O3), yttrium oxide, such as yttria (Y2O5), and / or hafnium oxide (HfO x ) is the NO of the catalytic article (1) x It serves to increase the adsorption capacity and its stability.

[0104] NO x A storage function may also be applied to the catalyst article (1), preferably to its bottom (In-B and Out-B) coating layers, more preferably to its Out-B coating layer. x Low NO during cold start of adsorption x Mass transfer is not as important when it occurs at high concentrations. The top layer is NO x It protects the bottom layer where the adsorbent material is located from many poisons (solids, larger HC, SO2 molecules) access.

[0105] La, Y, Hf and Ce oxides are NO x These are often separated from the top layer in the preferred embodiment of the present disclosure, either fresh or after hydrothermal aging, as they block Pt and Pd sites in the oxidation reaction and increase the ignition temperature. NO2 is primarily formed in the top layer, which contains the higher PGM loading, and rapid pore diffusion transports NO2 to the bottom layer, where it dissociates from the weakly bound metal-NO x The same metal oxides are adsorbed on these adsorbents as sulphur oxides (SO x ), and therefore has the ability to adsorb sulfur oxides (SO x) is occluded in layers with low or no PGM loading.

[0106] If present, La2O3, Y2O5 and / or HfO x The amount of La2O3, if used, ranges from about 1 to 10 g / L, preferably 3 to 6 g / L, as stable oxide in the portion of the catalyst article (1). The amount of La2O3 in the coating, if present, should vary from 1 to 15 wt% in the layer. Lanthanum is preferably used in the bottom layer to provide NO x and S.O. x It gives rise to an adsorption capacity and improves the absolute thermal durability near the surface of the substrate (2), thereby making it possible to maintain good mechanical stability of the layer even at high temperatures.

[0107] In the catalyst article (1) of the present disclosure and preferred embodiment, the upper layer is adapted to reduce NO x NO from the adsorbent x This prevents the desorption (diffusion and heat transfer) of the ions from occurring too rapidly.

[0108] In the catalyst article (1) of the present disclosure, NO x The adsorbent, e.g., cerium oxide, is held as bulky, large particles and has high NO x The Pt-Pd layer provides adsorption capacity while the PGMs are retained as finely dispersed small particles to provide high catalytic activity, and Pt in particular is known to be highly chemically resistant to poisoning. Conversely, the rapid access of high concentrations of HC to the Pt-Pd sites limits diffusion during DPF regeneration. Therefore, in the preferred embodiment of the present disclosure, it is important that the top layer has a higher PGM concentration than the bottom layer.

[0109] In a preferred embodiment of the catalyst article (1) of the present invention, the bottom coating layer of the catalyst article (1) is a defined cerium oxide (CeO x ), lanthanum oxide, yttrium oxide and / or hafnium oxide, which may also be stabilized mixed oxides, where the role of La, Y, Hf and Ce oxides is to suppress NO xIn some embodiments, the bottom layer may be free of Al, Ti and Si oxides, or even contain only the defined Ce, La, Y and / or Hf oxides or mixtures thereof, together with optional PGMs.

[0110] SO x The adsorption strength of SO is higher on these La, Y, Hf and Ce oxide adsorbents than on alumina, for example, thereby allowing selective SO adsorption onto Ce, La, Y and Hf oxides. x Allows adsorption of SO onto alumina x Optionally, the bottom coating layer may be used to reduce the NO x To improve storage activity, the PGM loading is low. This bottom coating layer can include both Pt and Pd in ​​a Pt:Pd ratio of about 1:9 to about 9:1.

[0111] Preferably, the bottom layer is NO x To enhance the storage function, it has a composition of only Pt or Pd with a lower PGM loading (<0.8 g / L, preferably <0.4 g / L, more preferably <0.2 g / L). The Pt in the bottom layer acts as a barrier to NO diffusion in addition to the gas phase NO2 diffusion from the top layer. x It is applied to enhance the in situ oxidation of NO to NO2 near the adsorbent.

[0112] NO x The location of the adsorbent material can be more precisely designed for optimal utilization. x and S.O. x The La, Y, Hf oxides as adsorbents are preferably located in the In-B coating layer, where NO x / SO x is more strongly adsorbed than the Ce compound. x The Ce oxide as an adsorbent is preferably located in the Out-B coating layer, where there is less amount of poison and inhibition of HC and CO, lower temperature during engine start-up, and higher NO2 concentration due to the Pt-rich top layer.

[0113] If the Pt-rich layer is better than the Pt / Pd-poor catalyst in the HC-SCR reaction, the NO2 formed and desorbed can be better utilized in the outlet coating layer. Of course, HC-SCR also proceeds in the inlet layer when the HC concentration is higher. NO2 with higher desorption temperature x When the adsorbent (La / Y / Hf) is located first in the flow direction, the desorbed NO x is able to pass through the outlet zone if it is not adsorbed onto any Ce compounds present.

[0114] When Ce is located only in the In-B layer and La / Hf / Y is located in the Out-B layer, the desorbed NO x is adsorbed at the downstream La / Y / Hf sites. Therefore, in a preferred embodiment, La, Y, and / or Hf are present in the optimal structure located in the In-B layer, and Ce or stabilized Ce is present in the Out-B layer. However, when focusing primarily on low temperature adsorption-desorption, both the In-B and Out-B coating layers may contain Ce.

[0115] NO adsorbed on adsorbents (e.g., Ce, La, Y, and Hf oxides, zeolites) x and S.O. x can be desorbed during passive (standard operation) or active regeneration. These compounds and PGM-zeolites are capable of desorbing NO at low temperatures (<200°C). x NO adsorption and desorption at lean exhaust gas conditions above 160-200°C x It has adsorption properties. Therefore, NO x is adsorbed at low temperatures when the downstream urea-selective catalytic reduction (SCR) catalyst is not yet activated and desorbed at the temperature when urea injection is initiated for SCR.

[0116] The adsorption-desorption characteristics of the catalyst article (1) are such that the overall NO 2 content is reduced, which is difficult in modern lean applications (e.g., diesel and H2 engines). xapplied to reach performance targets. If the adsorption-desorption characteristics are differentiated between the PGM-rich layer and the bottom layer, the characteristics do not prevent the PGMs from interacting with their optimal supports. Mass transport to the PGM sites in the upper layer is required to be rapid, e.g., DPF regeneration conditions (high HC), while the adsorbed compounds have more time to diffuse to the bottom layer at service conditions.

[0117] NO x The storage agent is the SO x If SO is also absorbed, x is distanced from the main PGM. x Adsorption and Nitrate / NO x In order to apply regeneration (decomposition) most efficiently, NO x / SO x Periodic enrichment with an adsorbent (λ<1.2, preferably <1.0) can also be applied to the catalyst article (1).

[0118] Under these conditions, NO x is easily desorbed and reduced at PGM sites at temperatures above 150°C. Ce, La, Y and Hf oxides are the preferred compounds for applications with enrichment of λ<1.2. NO x and S.O. x Recovery is especially important for SO x Conventional NO requires higher temperatures for decomposition. x These compounds are easier to use than storage elements such as barium (Ba) and potassium (K).

[0119] However, if the enrichment strategy is highly efficient in the system (λ<1.0), these types of NO x It is possible that an adsorbent, such as an alkaline earth metal, such as strontium (Sr) and Ba, may be present in the catalyst article (1). In diesel and dual fuel applications, the more strongly bound NO is at least partially adsorbed in the catalyst article (1) layer. x and S.O. xPeriodic DPF regeneration, which is the natural way for DPFs to break down, is still required.

[0120] NO of Ce compounds x The adsorption capacity is, for example, x Particle size and surface area (m 2 The NO2 concentration can be controlled by the amount of Ce per unit area (g / g). When Ce is added to the layer as Ce oxide particles, the original properties of the powder form material are selected to achieve the best functionality. By using a very high surface area material and small particle size, the highest NO2 concentration can be achieved. x Adsorption capacity is provided.

[0121] It is difficult to retain the original surface area if the temperature in the application is too high. However, the highest NO x The adsorption capacity was measured by the Brunauer-Emmett-Teller (BET) method at 250 m 2 / g~300m 2 / g, preferably 260m 2 / g~290m 2 / g range, but more preferably about 270 m 2 / g, and has a specific surface area between 1 μm and 10 μm, preferably 5 μm (d 50 ) average particle size (d 50 This was achieved with Ce oxide (Ce2) having the same structure.

[0122] This type of Ce oxide (Ce2) has a specific surface area (BET) of 140 m when freshly prepared. 2 / g, but the particle size is 11 μm (d 50 The Ce oxides with specific surface areas (BET) >200 m2 as fresh preparations still had obviously higher adsorption capacities after hydrothermal (HT) aging at 700 °C for 20 h than the other Ce oxides (Ce1), which had a larger adsorption capacity than the other Ce oxides (Ce2). The best adsorption capacity and release were observed for the Ce oxides with specific surface areas (BET) >200 m2 as fresh preparations. 2 / g, preferably >240m 2 / g. These Ce compounds are <10 μm (d 50 ), preferably <7 μm (d 50 ) can be defined by the original particle size distribution.

[0123] In addition to the high surface area of ​​CeO2, small CeO x Soluble Ce compounds can be used in the same layer to make the particles and also act as a binder. The role of the binder is to bind the larger solid particles together and create a mechanically durable porous layer with good adhesion to the surface of the substrate (2). Zr-stabilized Ce (ZrCe) oxide has a high adsorption capacity and specific surface area (BET) (182 m 2 Stabilization with Zr also prevents sulfur poisoning and improves thermal durability. In addition, cerium oxide promoted with manganese (Mn), titanium (Ti), and praseodymium (Pr) also improves NO x It can be used as an adsorbent material.

[0124] Zeolites with high Si / Al2 ratio (SAR, 5-1000, preferably 10-50), such as Beta, ZSM-5, Chabazite (CHA), AEI, Ferrierite (Fer), Y or combinations thereof, are preferably added to the bottom layer to enhance the production of hydrocarbons and / or NO at low temperatures. x The adsorption capacity can be increased. High SAR zeolites are good hydrocarbon storage materials without the need for additional metals.

[0125] But NO x And the adsorption of hydrocarbons can be chemically enhanced by impregnating these zeolites with Pd or Pt, drying, calcining and then adding them to the washcoat slurry. If used, zeolites with or without PGMs for storing hydrocarbons are preferably present in the In-B coating layer.

[0126] PGMs can also be added to washcoat slurries containing ready-to-use zeolites. Pd on zeolites (e.g., CHA, Beta, and Fer) can be used to disperse NO x It has adsorption properties. xZeolites containing Pd for adsorption are preferably present in the In-B layer. The presence of Pt and / or Pd on these zeolites (e.g., Beta, ZSM-5) promotes and activates the zeolites for the adsorption of hydrocarbons. The concentration of PGM ranges from 0.1 to 3.0 wt% of the dry zeolite weight. Preferably, Pd is added to CHA or Fer and Pt is added to Beta or ZSM-5.

[0127] The PGM components can be added to the washcoat slurry in the form of nitrates, ammonium / ammine compounds, chlorides, carbonates, sulfates, or combinations thereof. The total amount of PGM components in the coating layer ranges from about 0.1-10 wt% of the total weight of the coating, preferably 0.5-3 wt%. Ammonia, ammonium hydroxide and other inorganic hydroxides, as well as organic and inorganic acids, can be used to adjust the pH of the washcoat solution to improve washcoat activity, coverage and adhesion. If necessary, the PGM components can be pre-added directly to the raw material particles to ensure their high concentration and location in any layer.

[0128] The support and promoter components, such as aluminum, silicon, titanium, tungsten, cerium, zirconium, lanthanum, hafnium, and yttrium, and zeolites, can be added individually to the washcoat as ready-to-use powders, oxides, or their precursors (nitrates, carbonates, hydroxides, ammonium compounds), or can be added by direct impregnation into the catalyst article (1) layer from precursor solutions.

[0129] The support and promoter material components can also be added as their mixed oxides, such as Si-Al, Ti-Al, Zr-Al, La-Al, Si-Zr, Si-Zr-Al, Ce-Zr and Ce-Zr-Al oxides, to the washcoat or directly to the catalyst article (1) layer. The total amount of these materials in the catalyst article (1) ranges from about 50 to 200 g / L, more preferably from 100 to 150 g / L.

[0130] The disclosed disclosure has high hydrocarbon and CO oxidation activity in the front portion of the catalyst article (1), enabling high hydrocarbon oxidation, especially under DPF regeneration conditions (high hydrocarbon concentrations, e.g., >1% C1), where oxidation is inhibited by high hydrocarbons in conventional DOC or single PGM catalysts.

[0131] Higher Pd loading is essential to overcome the inhibition and improve thermal durability when the temperature rise is high during rapid oxidation of high hydrocarbon concentration using excess oxygen. Pt promotes the oxidation of certain hydrocarbons, increases chemical durability against, for example, sulfur, and forms a promoting interaction with Pd. The catalytic article (1) of the present disclosure also showed high NO to NO2 oxidation activity in the rear portion of the catalytic article (1).

[0132] The major part of the oxidation reaction takes place in the top coating layer of the catalytic article (1), preferably the In-T coating layer in which the PGMs are predominantly incorporated, and therefore the internal mass transport (pore diffusion) limitations are small even though the pores in the upper layer may be partially filled by deposition during long term use.

[0133] As shown by experiments, under DPF regeneration conditions, the In-T coating layer is more active for hydrocarbon oxidation than the Out-T coating layer. A longer (>50% of the total length of the substrate (2), preferably 55-70%) In-T coating layer with a defined PGM loading and Pt:Pd ratio is essential to overcome external and internal mass transfer limitations in the presence of high hydrocarbon concentrations. The longer the In-T coating layer, the longer the residence time for heat transfer in catalysis and exothermic reactions (HC / CO oxidation). If the total coating amount is increased by a thicker bottom layer, the back pressure increases and the radial flow distribution is improved, resulting in a higher hydrocarbon oxidation activity in DPF regeneration.

[0134] A thicker bottom layer with low / no PGM loading and adsorbent results in a higher adsorption capacity, which is the bottom layer for the adsorption of hydrocarbons and NO xThe amount of PGM can be used to store and remove NO. x NO on the adsorbent x If the adsorption sites are partially blocked, preferably less. Even if the length of the Out-T coating layer is shorter (<50%, preferably 30-45% of the total length of the substrate (2)), the shorter length is still long enough for the reaction to proceed in the rear part of the catalyst article (1).

[0135] While hydrocarbons and CO are mainly oxidized in the In-T coating layer, the Out-T coating layer is designed and optimized mainly for NO oxidation. The concentrations of exhaust gas components (NO, hydrocarbons, CO) are much lower in the rear part (Out-T coating layer), and a shorter length and a smaller amount of coating are sufficient to reach the target conversion under standard exhaust and DPF regeneration conditions.

[0136] In special cases, if the main function of the catalytic article (1) is to x If rapid adsorption-desorption is required and the amount of poisons in the exhaust gas is negligible, NO x The layer containing the adsorbent can be located as the top layer.

[0137] However, the same composition can be applied in layers according to the present disclosure (e.g., Figures 2 and 3). With high PGM amount in the bottom layer, the loss of PGMs due to erosion is very low, thereby protecting e.g. SCR catalysts against PGM poisoning, especially when the ATS does not have a DPF (H2 engine application).

[0138] The catalyst article (1) can be coated onto ceramic and metal substrates (2). The substrate (2) is preferably a flow-through type substrate (2), although wall-flow filter structures can be used in catalyst article (1) designs using layers.

[0139] According to the present disclosure, monolithic catalytic substrates (2) made from ceramic or metal are preferred.

[0140] As is known in the art, ceramic substrates (2) (honeycombs) typically have square cells, while most metal substrates (2) have sinusoidal corrugated channels, although other channel cross sections are possible in the present disclosure, including triangular, hexagonal, trapezoidal, or circular.

[0141] Substrates (2) suitable for use in the present disclosure have a cell density ranging from 10 to 2000 cells per square inch (cpsi), but preferably from 100 to 600 cpsi, as is customary for lean and diesel applications. When the substrate (2) is a ceramic substrate (2), a wall thickness of 10 to 500 μm is preferred for lean and diesel applications, more preferably between 50 to 200 μm. When the substrate (2) is a metal substrate (2), the wall thickness of the substrate is 20 to 200 μm, preferably 30 to 100 μm, or more preferably 40 to 60 μm.

[0142] The catalyst article (1) is coated by spraying, pouring, or immersing the washcoat onto the substrate (2), and any combination thereof, to achieve the correct amount and penetration depth and layer thickness of the washcoat inside the catalyst article (1). The surface and slurry properties are modified with typical organic agents to allow for an efficient coating process.

[0143] The active material, e.g., Pt group metals, can be added to the washcoat slurry or post-impregnated or chemisorbed onto the substrate (2) of the catalyst article (1) from a precursor solution comprising an organic or inorganic (typically aqueous) solvent after the porous support material has been added. The PGMs can be added to the feedstock and then to the washcoat.

[0144] In the front part of the catalyst article (1), the In-B coating layer is first coated on the surface of the uncoated part of the catalyst article (1) (substrate (2)), and the In-T coating layer is coated on top of the bottom coating layer. In the rear part of the catalyst article (1), the Out-B coating layer is first coated on the surface of the uncoated part of the catalyst article (1) (substrate (2)), and the Out-T coating layer is coated on top of the outlet coating layer.

[0145] Schematic diagrams of how these coating layers are located are shown in Figures 1 and 4-7, where s1, s2, s3, s4, s5 and s6 represent the (radial) coating thicknesses of the In-B, Out-B, In-T, Out-T, Mid-B and Mid-T coating layers, respectively. The (axial) lengths of each coating layer, L1, L2, L3, L4, L5, L6, can vary from 0 to L (L1+L2+L5≦L, L3+L4+L6≦L), so that the top layers are ideally not on top of layers at the same location in the flow direction (inlet, middle, outlet), as shown in Figure 4.

[0146] When the catalyst article (1) does not have an intermediate coating layer, the lengths (L1 and L2) of the In-B and Out-B coating layers are in the range of about 20-80%, preferably about 50%, of the total length of the catalyst article (1). Next, the lengths (L3 and L4) of the In-T and Out-T coating layers are in the range of about 20-80%, preferably 30-70%, more preferably 40-60%, of the total length of the catalyst article (1), with L3>L4.

[0147] When a Mid-B coating layer is applied to the catalyst article (1), the length of the In-B, Mid-B and Out-B coating layers is in the range of about 5-70%, more preferably about 33%, of the total length of the catalyst article (1). When a Mid-T coating layer is applied, the length of the In-T, Mid-T and Out-T coating layers is in the range of about 5-70%, more preferably 20-50%, of the total length of the catalyst article (1).

[0148] The thickness of each one of these layers (In-B, In-T, Out-B, Out-T) can be 1-100 μm, preferably 5-50 μm for lean and diesel applications. The total amount of coating of each coating layer can be about 10-200 g / L (grams of coating per liter of substrate volume), preferably about 40-100 g / L, more preferably about 50-80 g / L, of all layers of the catalytic article (1). In general, the catalytic article (1) composition can be prepared by any deposition method (e.g., ALE, sol-gel) including possible organic vapor precursors for the defined elements.

[0149] The In-B, Out-B, In-T and Out-T coating layers can also be superimposed on one another to create a mixed layer, which is a way to form additional intermediate coating layers (Mid-B and Mid-T) on the catalyst article (1) (FIG. 5).

[0150] The middle layer can include bottom (Mid-B) and top (Mid-T) layers as in Figure 5, or can include only a Mid layer as in Figure 6. The middle layer can also be prepared otherwise by adding some washcoat dosage towards the catalyst article (1) thus forming a different composition in the middle layer compared to the inlet and outlet layers. Thus, the total coating thickness / amount in the middle layer can be smaller or larger than the inlet and outlet layers as desired depending on the given external design target for the catalyst article (1) of the present disclosure.

[0151] The amount of coating will be more if overlapping is utilized in the preparation, and less if no overlapping is formed and opposite bottom or top layers are formed at the same coating depth from different directions.

[0152] Similarly, the PGM loading and Pt:Pd ratios are different for the outlet and inlet layers. The total PGM loading in the middle layer may be higher or lower compared to the inlet and outlet layers as a whole, or as single bottom and top layers. The benefit of a higher amount of coating is that a post-ignition region is created that has a higher amount of coating to balance the high heat generation.

[0153] A higher amount of coating creates more pressure drop in the channels, which allows the gas to flow radially uniformly throughout the channels. If the amount / thickness of the coating is high over only a short distance, the increase in total pressure drop is still small. The higher PGM loading possible in the middle layer has the benefit of achieving complete oxidation of hydrocarbons and CO faster.

[0154] Additionally, if the inlet and outlet PGM loadings and Pt:Pd ratios are very different due to being tuned for different reactions, it is possible to have an intermediate composition in the middle section, where the properties transition stepwise from the inlet composition to the outlet composition.

[0155] Depending on the application, it is possible to emphasize the properties of the inlet (higher hydrocarbon oxidation activity) or outlet (higher NO2 formation activity) layers, thereby achieving different catalytic outcomes simply by adjusting the section size. Varying the length of the inlet, middle and outlet layers results in a tool for optimizing the catalyst article (1) performance for the application.

[0156] In one embodiment (see FIG. 7), the catalyst article (1) of the present disclosure may also include a second top layer located on top of the other coating layers from the front or rear portion of the catalyst article (1) and includes PGM components, preferably Pt and Pd. The length of the second top layer, if present, ranges from 10 to 100%, preferably 20 to 40%, of the total length of the catalyst article (1).

[0157] NO in catalytic article (1)x The adsorbent material (Ce, La, Y, Hf and Ce mixed oxides or mixtures of these oxides, zeolitic materials) is applied during the cold operating phase during engine start-up or low speed / load operating conditions. NO x is deNO x In the catalytic article (1) located before the unit (e.g., SCR, LNT), NO is adsorbed in a cooling phase at less than 100-200° C., and then desorbed at elevated temperatures, ideally at standard operating conditions, of about 150-250° C., where the desorption temperature is set to 100° C. for the next adsorption phase. x Low enough to free up adsorption capacity, but high enough that, for example, downstream SCR catalysts and urea dosing are already operating.

[0158] NO x The adsorbent absorbs NO during transient operation where the temperature fluctuates between 100 and 250°C. x It is important that the material can adsorb and desorb the

[0159] In some embodiments, NO x Adsorption compounds (e.g. Ce compounds with high surface area, zeolites) are consequently selected in a way that they have these low temperature adsorption-desorption properties. Here, Ce mixed oxides with Zr, Ti, Mn and / or Pr are effective in adsorbing NO x Offers the potential to increase adsorption capacity or stability (heat resistance, sulfur resistance).

[0160] Conventional NO x The adsorbent (e.g., Ba) is x SO x Even if the low-temperature adsorbents (e.g., Ce compounds) can be adsorbed, the formed sulfate or adsorbed SO x was also more readily decomposed compared to, for example, Ba sulfate. x The adsorbent is aluminum silicate (zeolite) which absorbs SO x If no SO is adsorbed, x Pt is resistant to SO xIt is known that Pd remains durable in the presence of, for example, NO x When used in conjunction with an adsorbent material, Pd sulfate is decomposed under typical dilute conditions.

[0161] In addition, these NO x Sulfates that can be adsorbed onto the adsorbent are also decomposed during DPF or typical SCR catalyst regeneration (for sulfur removal) conditions (e.g., at about 600°C). x The sulfates on the adsorbent are not yet decomposed at 600°C under dilute conditions. La, Y, and Hf are x NO as combined with adsorbents (Ce compounds, zeolites) x The adsorption temperature window is extended to the mid-range (above 200° C.).

[0162] In one embodiment, the catalyst article (1) of the present disclosure can be applied as a single or multiple unit of an ATS to purify lean exhaust gas resulting from internal combustion of diesel, gasoline, natural gas, biofuel, synthetic HC mixtures, hydrogen, ammonia, or combinations thereof (multi-fuel applications), or as part of a hybrid (electric and internal combustion engine) application.

[0163] The ATS may also include DPF, oxidation catalyst, hydrolysis, SCR, and ammonia slip catalyst (ASC) units, with the catalyst article (1) unit usually located before other exhaust treatment units in the flow direction. x It is also possible that other ATS units, such as adsorption or special oxidation catalysts (eg, for methane oxidation), are located in front of this catalyst article (1).

[0164] The present disclosure explicitly or implicitly solves the above and below problems, and in particular relates to the following aspects and embodiments:

[0165] In a first aspect and embodiment, there is provided a catalytic article (1) for purifying an exhaust gas at lean exhaust gas conditions, said catalytic article (1) comprising flow channels (3) allowing an exhaust gas to traverse the catalytic article (1), thereby defining inlets and outlets for the exhaust gas and a flow direction of the flow channels for the exhaust gas traversing the catalytic article (1), the flow channels (3) providing a surface of a substrate (2) for carrying one or more catalytically active layers (11, 12, 21, 22) for converting at least a respective first and a respective second undesirable chemical component contained in the exhaust gas into at least a corresponding first or corresponding second desired chemical component during the passage of the exhaust gas through the catalytic article (1); - at least first and second catalyst sections (10, 20) are arranged on the substrate (2), each catalyst section (10, 20) comprising at least a respective first and a respective second catalyst layer (11, 12), (21, 22) arranged such that the respective first catalyst layer (11, 21) is proximal to the substrate (2) and the respective second catalyst layer (12, 22) is distal to the substrate (2); - each of the first and second catalyst layers (11, 12, 21, 22) is chemically different from the other; - a first catalyst section (10) is disposed in the flow path (3) such that the exhaust gas, while traversing the flow path (3), first encounters the first catalyst section (10) and then encounters the second catalyst section (20); - the second catalytic section (20) promotes, and the first catalytic section (10) does not substantially promote, the catalytic conversion of either the first or second undesired chemical constituent into the corresponding first or second desired chemical constituent; Catalyst article (1).

[0166] The present invention relates in a further aspect to a catalytic article (1) for purifying exhaust gases at lean exhaust gas conditions, providing a surface of a substrate, wherein the surface of the substrate is provided with inlet and outlet coating compositions defined by a flow direction, each inlet and outlet coating composition comprising at least a respective inlet and outlet proximal coating layer adhered to the surface of the substrate, and a respective inlet and outlet distal coating layer adhered to the respective inlet and outlet proximal coating layer, each coating layer comprising porous Al, Si and / or Ti oxide for diffusion exchange with a traversing exhaust gas to bring the exhaust gas into contact with the respective catalytic coating layer; a. the inlet-proximal (In-B) coating layer is located at the inlet of the catalytic article (1) and comprises one or more catalytically active metals selected from platinum group metals (PGMs) including Pt, Pd, Rh, Ir, Ru, Os, or precious metals as Ag or Au, in a loading of less than 0.8 g / L; b. the inlet-distal (In-T) coating layer is located at the inlet of the catalytic article (1) and comprises one or more catalytically active metals selected from platinum group metals (PGMs) including Pt, Pd, Rh, Ir, Ru, Os, Ag, and precious metals as Ag or Au in a loading of 0.5 to 7.0 g / L; c. the outlet-proximal (Out-B) coating layer is located at the outlet of the catalytic article (1) and comprises one or more catalytically active metals selected from platinum group metals (PGMs) including Pt, Pd, Rh, Ir, Ru, Os, or precious metals as Ag or Au, in a loading of less than 0.8 g / L; d. The outlet-distal (Out-T) coating layer is placed at the outlet of the catalytic article (1) and comprises one or more catalytically active metals selected from platinum group metals (PGMs) including Pt, Pd, Rh, Ir, Ru, Os, or precious metals as Ag or Au in an amount of 0.1 to 2.0 g / L; e. The outlet distal (Out-T) coating layer comprises a tungsten (W), molybdenum (Mo), and / or zirconium (Zr) compound, more preferably a tungsten compound, to promote the oxidation of NO to NO2.

[0167] In that embodiment, the inlet and / or outlet proximal (In-B and Out-B) coating layers are x To promote adsorption-desorption and NO2 formation by desorption below 200°C, cerium (Ce) oxide or mixed cerium oxides, such as ZrCe, MnCe, TiCe, PrCe oxides, or combinations thereof.

[0168] Typically, cerium (Ce) oxide or mixed cerium oxides, such as ZrCe, MnCe, TiCe, PrCe oxides, or combinations thereof, are used. 2 / g, preferably above 200m 2 / g, more preferably 230m 2 / g.

[0169] In a further embodiment, the cerium (Ce) oxide or cerium mixed oxide, such as ZrCe, MnCe, TiCe, PrCe oxide, or a combination thereof, has a particle size (d 50 ) in the form of solid particles.

[0170] In yet further embodiments, the inlet and / or outlet proximal (In-B and Out-B) coating layers comprise NO x Lanthanum (La), yttrium (Y) and hafnium (Hf) or combinations thereof are included to promote adsorption.

[0171] In a further embodiment, the inlet and / or outlet proximal (In-B and Out-B) coating layers are resistant to HC and NO x To facilitate adsorption, Beta, ZSM-5, CHA, Fer and AEI zeolites or combinations thereof are included.

[0172] In yet a further embodiment, the middle coating layers, mid-proximal (Mid-B) and mid-distal (Mid-T), are created between the inlet coating composition and the outlet coating composition.

[0173] In a further embodiment, the inlet and / or outlet proximal (In-B and Out-B) coating layers have a length of about 20-80%, more preferably about 50%, of the total length of the substrate (2), and the inlet and / or outlet distal (In-T and Out-T) coating layers have a length of about 20-80%, preferably about 30-70%, more preferably about 30-70%, with the In-T being longer than the Out-T layer.

[0174] In yet a further embodiment, the amount of coating for each coating layer may be about 10-200 g / L, preferably about 40-100 g / L, and more preferably about 50-80 g / L, of all layers of the catalyst article (1).

[0175] In a further embodiment, the Pt:Pd ratio in the inlet-distal (In-T) coating layer is in the range of 1:4 to 5:1, preferably 1:1 to 4:1, more preferably 2:1 to 3:1, and the Pt:Pd ratio in the outlet-distal (Out-T) coating layer is in the range of 3:1 to 30:1, preferably 4:1 to 15:1, more preferably 5:1 to 10:1, or the Pt:Pd ratio in the Out-T coating layer can also be 1:0 (only Pt, no Pd).

[0176] In yet a further embodiment, the inlet-distal (In-T) coating layer is more active in oxidizing carbon-containing components than the outlet-distal (Out-T) coating layer, and the Out-T coating layer is more active in oxidizing NO to NO2 than the In-T coating layer.

[0177] In a further aspect, the present disclosure can be utilized to purify average lean exhaust gas emissions resulting from the internal combustion of diesel, gasoline, biofuels, hydrogen, ammonia, natural gas, and combinations thereof, and oxidize hydrocarbons (HC), carbon monoxide (CO), hydrogen (H2), ammonia (NH3), and nitric oxide (NO) to produce nitrogen oxides (NO) under normal operating conditions, as well as under particulate filter and catalyst regeneration conditions. x ), sulfur oxides (SO x), and hydrocarbons (HC), or any combination thereof, according to any one of the above and other embodiments described herein below. EXAMPLES

[0178] Sample preparation - methods Catalyst articles (1) of the present disclosure and reference samples were prepared by adding one or more washcoat slurries in a specific order onto a flow-through ceramic substrate (2) having a cell density of 400 cpsi and a wall thickness of 100 μm, or a metal substrate (2) having a cell density of 300 cpsi and a wall thickness of 50 μm after rolling. The washcoat slurries include platinum group metal (PGM) components (Pt and Pd), alumina, and other raw materials, which are identified in more detail in the examples.

[0179] The first Al compound and other possible metal oxide precursors were diluted with deionized water. The slurry was milled in a ball mill or continuous mill for several hours until the washcoat slurry reached the target particle size. The PGM components and other possible raw materials were added along with the pre-milled slurry, where water was the predominant liquid.

[0180] The ready-to-use washcoat slurry was applied onto a ceramic substrate (2) by dipping, pouring, aspirating, or spraying the washcoat to obtain a target amount of washcoat on the catalyst article (1) of the present disclosure and on the reference sample. If necessary, the ready-to-use washcoat slurry was brushed onto a metal foil.

[0181] The amount of washcoat was adjusted based on the amount of the aqueous slurry, and the solid content in the aqueous slurry was measured. The coated catalyst article (1) of the present disclosure and the reference sample were dried in air flow at 60-120°C after each coating step to remove excess water.

[0182] The catalyst article (1) of the present disclosure and the reference sample were calcined in a static air oven at 550° C. for 1 hour between additions of coating layers, and at 550° C. for 4 hours after addition of all coating layers.

[0183] The final calcination temperature, calcination time and heating gradient can be selected based on the precursor and target properties of the washcoat slurry used to enable good adhesion and high activity of the catalyst article (1).

[0184] For example, the final calcination temperature may range from about 500° C. to about 700° C. The amount of coating (g / L, grams of coating per liter of substrate volume) was calculated based on the final weight of the catalyst article (1) and the reference sample after calcination. More precisely, the difference between each catalyst article (1) and the reference sample is described in Table 1 and Examples 1-12. [Table 1-1] [Table 1-2]

[0185] The compositions of the experimental and test samples in Table 1, except for the single layer compositions, were described according to the general structure detailed in Figure 1. Therefore, for samples with the same top or bottom layer composition, it means that in the experiments, In-T and Out-T had the same composition, or In-B and Out-B had the same composition.

[0186] Many of the samples in Table 1 were optimized for the catalytic article (1) composition to provide optimal discrimination between HC / CO oxidation, NO to NO2 oxidation, or NO x The composition of the inlet or outlet layers was separately made to be optimized for the adsorption-desorption properties, in a way to better explore the effect of a single variable, according to the inventors' realization that the effect of a zoned catalyst section is primarily an additive effect of two or more zoned sections present in the catalyst article (1).

[0187] Finally, samples with four different layer compositions (In-T, In-B, Out-T and Out-B coating layers) were examined with the sample of Example 12 to investigate the overall functionality of the catalytic article (1) comprising two catalytic sections (10, 20).

[0188] (Example 1) An example of different porous coatings located in bottom and top layers on a ceramic substrate (2) (2.5L for full size test) as shown in Figure 2. The bottom coating layer contained 100 wt% alumina and no PGM components. In preparing the coating for the top layer of the catalyst article (1), tungsten and platinum precursor materials were added to a slurry containing pre-milled alumina.

[0189] After coating, drying and firing, the coating layer contained 87.9 wt% alumina, 10.6% tungsten oxide (WO3) and 1.52 wt% platinum. The total PGM loading for this example was 0.88 g / L Pt; this example contained no Pd.

[0190] The coating compositions of the inlet bottom (In-B) and outlet bottom (Out-B) layers were the same. The inlet top (In-T) and outlet top (Out-T) coating layers also had the same composition according to the structure of FIG.

[0191] This example was conducted to show that W applied to the Out-T coating layer in the catalyst article (1) promotes NO2 formation.

[0192] In the context of the present disclosure, the layered coated catalyst article (1) according to Example 1 is suitable for use as the outlet section (20) of the catalyst article (1) of the present invention.

[0193] (Example 2) A single coating layer containing tungsten was applied in this example according to the prior art and FIG. 2 (substrate (2), 2.5 L for full size test), where the tungsten and platinum precursor materials were added to a slurry containing pre-milled alumina.

[0194] After coating, drying and calcination, the coating layer contained 93.9 wt% alumina, 5.3% tungsten oxide and 0.76 wt% platinum. The PGM loading in this example was 0.88 g / L Pt, and this example contained no Pd. The composition can be applied to the catalyst article (1) as an example layer with W promotion.

[0195] (Example 3) reference The prior art reference oxidation catalyst had a single coating layer on a ceramic substrate (2) (2.5L for full size test). The coating layer contained 99.2wt% alumina and 0.76wt% platinum. The PGM loading in this example was 0.88g / L Pt (no Pd).

[0196] The results of Examples 1-3 are shown in FIG. 8, which details how the oxidation of NO to NO can be positively affected by the top layer (Examples 1 and 2) having a bi-layered structure containing both tungsten (W) and platinum and / or palladium, demonstrating the suitability of such a bi-layered structure as an outlet compartment in accordance with the present disclosure.

[0197] (Example 4) In this example, different porous coatings were located at the bottom and top coating layers on the ceramic substrate (2) (for SGB testing), as shown in FIG. 3.

[0198] The bottom coating layer contained 100 wt% alumina and no PGM components. The coating compositions of the inlet bottom (In-B) and outlet bottom (Out-B) coating layers were the same.

[0199] The inlet-top (In-T) coating layer was present at the front portion of the catalyst article (1) according to the flow direction and contained 99.2 wt% alumina, 0.61 wt% platinum and 0.15 wt% palladium. In the outlet-top (Out-T) washcoat, tungsten and platinum precursor materials are added to a slurry containing pre-milled alumina.

[0200] After coating, drying and firing, the Out-T coating layer contained 93.9 wt% alumina, 5.3% tungsten oxide and 0.76 wt% platinum. The PGM loading in the front (inlet) section was 0.88 g / L PGM with a Pt:Pd ratio of 4:1. The PGM loading in the rear (outlet) section was 0.88 g / L Pt (no Pd).

[0201] The average PGM loading in this example was 0.88 g / L PGM with a Pt:Pd ratio of 9: 1. The inlet top (In-T) and outlet top (Out-T) coating layers had different compositions and Pt:Pd ratios.

[0202] This example of catalyst article (1) was conducted to show that Pt:Pd in ​​the In-T coating layer together promotes HC / CO oxidation, and tungsten (W) in the Out-T coating layer together with Pt promotes NO2 formation, thereby demonstrating the feasibility of the catalyst article (1) of the present disclosure having a compartmentalized coating structure and simultaneously promoting both HC / CO oxidation and NO oxidation to NO2.

[0203] (Example 5) In this example, different porous coatings were located in the bottom and top layers on the ceramic substrate (2) (for SGB testing) as shown in Figure 2. The bottom coating layer contained 100 wt% alumina and no PGM components. The coating composition of the inlet bottom (In-B) and outlet bottom (Out-B) coating layers was the same.

[0204] In preparing the top coating layer, tungsten and platinum precursor materials are added to a slurry containing pre-milled alumina. After coating, drying, and firing, the coating layer contained 93.9 wt% alumina, 5.3% tungsten oxide, and 0.76 wt% platinum. The PGM loading in this example was 0.88 g / L Pt and no Pd. The inlet top (In-T) and outlet top (Out-T) coating layers also had the same composition.

[0205] This example was conducted to show that W applied to the Out-T coating layer in the catalyst article (1) promotes NO2 formation.

[0206] In the context of the present disclosure, the layered coated catalyst article (1) according to Example 5 is suitable for use as the outlet section (20) of the catalyst article (1) of the present invention.

[0207] (Example 6) In this example, different porous coatings were located in the bottom and top layers on the ceramic substrate (2) (for SGB testing) as shown in Figure 2. The bottom coating layer contained 100 wt% alumina and no PGM components. The coating compositions of the inlet bottom (In-B) and outlet bottom (Out-B) coating layers were the same. The top coating layer contained 99.2 wt% alumina, 0.61 wt% platinum and 0.15 wt% palladium. The PGM loading in this example was 0.88 g / L PGM with a Pt:Pd ratio of 4:1.

[0208] This catalyst example was performed to show that the Pt:Pd in ​​In-T coating layer in the catalyst article (1) promotes HC / CO oxidation.

[0209] In the context of the present disclosure, the layered coated catalyst article (1) according to Example 6 is suitable for use as the outlet section (10) of the catalyst article (1) of the present invention.

[0210] (Example 7) A catalyst article (1) (for SGB testing) with different porous coatings located in the bottom, In-T and Out-T coating layers on a ceramic substrate (2) as shown in Figure 3. The bottom coating layer contained 100 wt% alumina and no PGM components.

[0211] The coating compositions of the inlet bottom (In-B) and outlet bottom (Out-B) coating layers were the same. The inlet top (In-T) coating layer was present at the front part of the catalyst article (1) according to the flow direction and contained 99.2 wt% alumina, 0.61 wt% platinum and 0.15 wt% palladium. For the outlet top (Out-T) coating, tungsten and platinum precursor materials are added to a slurry containing pre-milled alumina.

[0212] After coating, drying and firing, the Out-T coating layer contained 93.9 wt% alumina, 5.3% tungsten oxide and 0.76 wt% platinum. The PGM loading in the front section was 0.88 g / L PGM with a Pt:Pd ratio of 4:1. The PGM loading in the rear section was 0.88 g / L Pt with no Pd. The average PGM loading in this example was 0.88 g / L PGM with a Pt:Pd ratio of 9:1. Therefore, the inlet top (In-T) and outlet top (Out-T) coating layers had different compositions and Pt:Pd ratios.

[0213] This example of catalyst article (1) was made to show that Pt:Pd in ​​the In-T layer together promotes HC / CO oxidation, and W in the Out-T coating layer together with Pt promotes NO2 formation, demonstrating the feasibility of separating these two catalytic processes in the same catalyst article (1) in the context of the present invention.

[0214] (Example 8) In this reference example, different porous coatings were located on the ceramic substrate (2) at the bottom, In-T and Out-T coating layers (for SGB testing), as shown in FIG.

[0215] The bottom coating layer contained 100 wt% alumina and no PGM components. The coating compositions of the inlet bottom (In-B) and outlet bottom (Out-B) coating layers were the same. The inlet top (In-T) coating layer was present at the front part of the catalyst article (1) according to the flow direction and contained 99.2 wt% alumina, 0.61 wt% platinum and 0.15 wt% palladium.

[0216] The Out-T coating layer was present at the rear portion of the catalyst article (1) according to the flow direction and contained 99.5 wt. % alumina, 0.68 wt. % platinum and 0.08 wt. % palladium. The PGM loading in the front portion was 0.88 g / L PGM with a Pt:Pd ratio of 4:1. The PGM loading in the rear portion was 0.88 g / L PGM with a Pt:Pd ratio of 9:1. The average PGM loading in this example was 0.88 g / L PGM with a Pt:Pd ratio of 5.7:1. Therefore, the In-T and Out-T coating layers had different compositions and Pt:Pd ratios.

[0217] This example was performed to show the effect of Pt:Pd ratio in W-free In-T and Out-T coating layers on HC / CO / NO oxidation.

[0218] (Example 9) In this catalyst article (1), different porous coatings were located on the ceramic substrate (2) at the bottom, In-T and Out-T coating layers (for SGB testing), as shown in FIG.

[0219] The bottom coating layer contained 100 wt% alumina and no PGM components. The coating compositions of the inlet bottom (In-B) and outlet bottom (Out-B) coating layers were the same. The inlet top (In-T) coating layer was present at the front part of the catalyst article (1) according to the flow direction and contained 99.2 wt% alumina, 0.51 wt% platinum and 0.25 wt% palladium.

[0220] For the Out-T washcoat, tungsten and platinum precursor materials are added to a slurry containing pre-milled alumina. After coating, drying, and firing, the Out-T coating layer contained 93.9 wt% alumina, 5.3% tungsten oxide, and 0.76 wt% platinum. The PGM loading in the front section was 0.88 g / L PGM with a Pt:Pd ratio of 2:1. The PGM loading in the rear section was 0.88 g / L Pt (no Pd). The average PGM loading in this example was 0.88 g / L PGM with a Pt:Pd ratio of 5:1. Therefore, the In-T and Out-T coating layers had different compositions and Pt:Pd ratios.

[0221] This example of catalyst article (1) was conducted to show that Pt+Pd in ​​the In-T coating layer together promote HC / CO oxidation, and W in the Out-T coating layer together with Pt promotes NO2 formation.

[0222] (Example 10) In this example, different porous coatings were located on the ceramic substrate (2) at the bottom, In-T and Out-T coating layers (for SGB testing), as shown in FIG.

[0223] The bottom coating layer contained 100 wt% alumina and no PGM components. The coating compositions of the inlet bottom (In-B) and outlet bottom (Out-B) coating layers were the same.

[0224] The inlet-top (In-T) coating layer was present in the front section and contained 99.2 wt% alumina, 0.51 wt% platinum, and 0.25 wt% palladium. The Out-T coating layer contained 99.2 wt% alumina, and 0.76 wt% platinum. The PGM loading in the front section was 0.88 g / L PGM with a Pt:Pd ratio of 2:1. The PGM loading in the rear section was 0.88 g / L Pt (no Pd).

[0225] The average PGM loading in this example was 0.88 g / L PGM with a Pt:Pd ratio of 5: 1. Therefore, the inlet-top (In-T) and outlet-top (Out-T) coating layers had different compositions and Pt:Pd ratios.

[0226] This example was performed to show the effect of Pt:Pd ratio in W-free In-T and Out-T coating layers on HC / CO / NO oxidation.

[0227] (Example 11a~k) In these examples, different porous coatings were located in the bottom and top coating layers on the ceramic substrate (2) (for SGB testing) as shown in Figure 2. The bottom coating layers contained Pt-Ce1 (examples 11a-b), Ce1 (11c), Pt-ZrCe-La (11d), Pt-ZrCe (11e), Pd-Fer (11f) and Pt-alumina (coded Pt / Al) (11g), Pt-Ce2 (11h-i) and alumina (11j-k), respectively. Ce1 and Ce2 were added as ready-to-use powders: 149m 2 / g and d of 11 μm 50 Ce1, 270m 2 / g and d of 5 μm 50 Ce2, 182m 2 / g and d of 12 μm 50 ZrCe. Ce nitrate is used as a binder and additional NO x It was used along with other Ce materials as an adsorbent source.

[0228] However, it was found that Al sol or other binders could also be applied as binders. Therefore, the Ce1 and Ce2 bottom layers contained only Ce, and the ZrCe layer contained Ce and Zr. Ce, La, and ZrCe were present in the coating layers as their stable oxides or mixtures thereof under the conditions of use (e.g., CeO2, La2O3, ZrO2, generally CeO x , LaO x , ZrO x La was added as a La nitrate solution and Zr was added as a Zr nitrate solution, resulting in good dispersion of Zr and La in the otherwise porous material.

[0229] Therefore, the 11d sample contained Zr, Ce and La in the final layer. The exact oxidation state of the metal oxides depends on the temperature and gas composition in preparation and use. These compounds can also form aluminates in the presence of Al oxide.

[0230] The coating composition of the inlet bottom (In-B) and outlet bottom (Out-B) coating layers of each single example was the same. Examples 11a, b, d, e, g, h, i contained 0.15 wt% platinum, example 11f contained 0.15 wt% palladium, and examples 11c, j, k had no PGMs in the inlet and outlet bottom layers. The inlet top (In-T) and outlet top (Out-T) coating layers were the same composition in each single example. Examples 11a, c, d, e, g, i, j contained 5.3 wt% tungsten oxide with 0.76 wt% platinum, and examples 11b, f, h, k contained 0.15 wt% palladium with 0.61 wt% platinum. The total PGM loading for Examples 11a, b, d, e, f, g, h, i was 1.06 g / L PGM and for Examples 11c, j, k was 0.88 g / L PGM.

[0231] In the context of the present disclosure, Example 11 illustrates the variability for the desired outlet compartment chemistry in the presence of tungsten (W) (Examples 11a, c, d, e, g, i, j) and comparative prior art examples suitable for use in the inlet compartment chemistry (Examples 11b, f, h, k).

[0232] (Example 12a~d) In these catalyst articles (1) of the present disclosure, four different porous coating compositions were located in In-T, In-B, Out-T and Out-B coating layers on the ceramic substrate (2) as shown in FIG. 17 (for SGB testing).

[0233] These inlet and outlet layers were prepared by the materials and methods described in Example 11. The In-B coating layers included Pt-Ce2 (12a-b), Pd-Fer (12c) and alumina (12d), with the coating layers either containing 0.15 wt% platinum (Examples 12a,b) or 0.15 wt% palladium (Example 12c) or no PGM (Example 12d). The Out-B layers included Pt-Ce2 (12a,c) and alumina (12b,d), with the coating layers either containing 0.15 wt% platinum (Examples 12a,c) or no PGM (Examples 12b,d). Thus, Example 12d serves as a comparison for Examples 12a-c.

[0234] The In-T coating layer contained 0.61 wt% platinum and 0.15 wt% palladium (Examples 12a-d). The Out-T coating layer contained 0.76 wt% platinum and 5.3 wt% tungsten oxide (Examples 12a-d). The total PGM loading was 1.06 g / L PGM for Examples 12a,c, 0.97 g / L PGM for Example 12b, and 0.88 g / L PGM for Example 12d. The inlet top (In-T) and outlet top (Out-T) coating layers of each single example had different compositions and Pt:Pd ratios. The inlet bottom (In-B) and outlet bottom (Out-B) coating layers of this example had various compositions and PGMs.

[0235] Examples of these catalyst articles (1) are that Pt+Pd in ​​the In-T coating layer together promote HC / CO oxidation, W in the Out-T coating layer together with Pt promotes NO2 formation, and NO x NO used for removalx This was done to demonstrate enhanced adsorption-desorption properties.

[0236] Activity measurement - test Test Method The catalytic activity of small cylindrical test-size samples (14 mm diameter, 75 mm length) was investigated by synthetic gas bench (SGB) experiments. The test-size samples were placed on a full-size ceramic substrate (2) (1.2 dm 3 ) or wound from a coated metal foil and then placed in a tubular metal tube reactor. Samples were tested 1) as new, or 2) after hydrothermal aging (HT) at 700°C for 20 hours (HO vapor concentration was 10 vol% during aging), or 3) after hydrothermal aging at 700°C for 20 hours and sulfur dioxide (SO2) aging at 400°C for 20 hours (SO2 concentration was 25 ppm during aging).

[0237] The activity of the samples was studied in a light-off test using two gas mixtures that mimicked diesel exhaust gas compositions: 1) 10 ppm C 10 H 22 (decane), 10 ppm C7H8 (toluene), 40 ppm C3H6 (propene), 300 ppm CO, 500 ppm NO, 10% O2, 6% H2O, 6% CO2, balance nitrogen (N2), and a space velocity (SV) of 50,000 h -1 and 2) a regeneration gas mixture (named “Regeneration” in FIG. 10) consisting of 4000 ppm C3H6, 2000 ppm CO, 200 ppm NO, 6% O2, 6% H2O, 6% CO2, balance N2, with a space velocity of 50.000 h -1 It was.

[0238] The activity of the samples was tested in THC oxidation (THC light-off temperature (temperature at which 50% THC conversion was achieved)) and in the oxidation of NO to NO2 during the light-off test.

[0239] The activity of the SGB test sample was alsox Adsorption / desorption experiments were studied. The studied samples were first pretreated with a gas mixture containing 13% O2, 6% H2O and balance N2 at 500 °C for 10 min and subsequently cooled to 120 °C in the same gas mixture. The NO adsorption phase was carried out at 120 °C in a gas mixture containing 100 ppm NO, 13% O2, 6% H2O and balance N2.

[0240] Next, NO x The desorption phase was carried out by heating the sample from 120° C. to 500° C. (10° C. / min) in a gas mixture containing 6% H2O and balance N2. The space velocity was 50,000 h o for all test phases. -1 It was.

[0241] NO x Adsorption capacity (μmol / g コーティング ) to NO x NO measured during the adsorption and desorption phases x Defined based on quantity. NO x may be physically or chemically adsorbed onto the catalyst surface and onto the adsorbent, for example as a nitrate or nitrite salt or precursors thereof.

[0242] NO detected by desorption x The adsorption capacity was higher for more strongly bound NO than for the stepwise exchange method. x Regarding NO by temperature x The emission directly indicates the adsorption strength, which is x NO FOR CONTROL x This is an important property in adsorption applications.

[0243] The total adsorption capacity was calculated by dividing the NO x In addition, it was also calculated for low-temperature desorption in the range of 120 to 200 °C. x (0-1.0 or 0-100%) is the cumulative amount of NO desorbed until the sample reaches a certain temperature (e.g., 200°C). x and the ratio of NO desorbed during the heating phase. x The definition was based on the total amount of

[0244] Full size sample (2.5dm in the example) 3 The catalytic activity of ) was investigated at steady-state conditions in a diesel engine experiment. Samples were studied 1) as fresh or 2) after hydrothermal aging at 700 °C for 5 h (HO vapor concentration of 10 vol.% during aging).

[0245] In the engine experiments, exhaust gas from an Agco Sisu 4.9L was used, and the space velocity ranged from 50,000 to 250,000 h o depending on the engine speed and torque. -1 The activity of the samples in the oxidation of NO to NO2 was studied during steady-state experiments. More precisely, each SGB and diesel engine experiment is described in the test results in Figures 8-17 and Tables 2-3.

[0246] Test results Test results in Figure 8 The activity of the catalyst article (1) according to Example 1, the composition of the coating layer according to Example 2, and the reference catalyst according to Example 3 were investigated as new in steady-state engine experiments, and the results are shown in FIG.

[0247] The results of Examples 1, 2 and 3 differed from each other with respect to the oxidation of NO to NO2. The oxidation of NO to NO2 for the layered sample containing W+Pt (Example 1) was 6-14% higher than the monolayer sample containing Pt (Example 3) at 220-380°C. The oxidation of NO to NO2 for the monolayer sample containing W+Pt (Example 2) was 3-6% higher than the monolayer sample containing Pt (Example 3) at 220-380°C.

[0248] The results clearly show that tungsten and the bilayer structure promote NO2 formation compared to the tungsten-free monolayer sample.

[0249] Test results in Figure 9 The activity of the catalyst articles (1) according to Examples 4 and 5, as well as the reference catalyst according to Example 6, was investigated in a synthetic gas bench (SGB) in a light-off experiment, as well as hydrothermally aged at 700° C. (HT700). The results are shown in FIG. 9. The results of the examples differed from each other with respect to the oxidation of NO to NO2. The results are shown regarding the effect of tungsten and zone coating on the studied catalyst articles (1).

[0250] According to this embodiment, the oxidation of NO to NO2 for the sample containing Pt+Pd in ​​the In-T coating layer and W+Pt in the Out-T coating layer (Example 4) as well as the sample containing W+Pt in the upper layer (Example 5) was 7-20% higher than the oxidation of NO to NO2 for Pt+Pd in ​​the upper layer (Example 6) at 210-350°C.

[0251] The results clearly show that the use of W+Pt instead of Pt+Pd in ​​the Out-T coating layer improves NO2 formation.

[0252] Figure 10 Test results The activity of the catalyst articles (1) according to Examples 4 and 5, and the reference catalyst according to Example 6, was investigated in a synthetic gas bench (SGB) in a light-off experiment, as well as HT700 aged. The results are shown in FIG. 10. The examples of catalyst articles (1) differed from each other in terms of THC light-off temperature. The results are shown regarding the effect of tungsten and zone coating on the studied catalyst articles (1).

[0253] According to this embodiment, the THC ignition temperatures of the sample with zones containing Pt+Pd in ​​the In-T coating layer and W+Pt in the Out-T coating layer (Example 4) and the sample with Pt+Pd in ​​the top layer (Example 6) were 4-12° C. lower than the THC ignition temperature of the sample with W+Pt in the top layer (Example 5) under the standard gas mixture. Under the regeneration gas mixture, the THC ignition temperatures of the samples of Examples 4 and 6 were 26-32° C. lower than the THC ignition temperature of Example 5.

[0254] The results show that the use of Pt+Pd in ​​the In-T coating layer is necessary for high THC oxidation activity at low temperatures.

[0255] Test results in Figure 11 The activity of the catalyst article (1) according to Example 7 and the reference catalyst according to Example 8 was investigated in a synthetic gas bench (SGB) in a light-off experiment and aged at HT700°C. The results regarding the effect of tungsten and Pt:Pd ratio for the catalyst article (1) are shown in Figure 11.

[0256] According to this embodiment, the sample containing Pt+Pd in ​​the In-T coating layer and W+Pt in the Out-T coating layer (Example 7) was able to achieve the same oxidation of NO to NO2 as the sample containing Pt+Pd in ​​both the In-T and Out-T coating layers (Example 8), proving the effectiveness of using tungsten as a cheaper substitute for platinum and palladium in the catalytic article (1) for oxidizing NO to NO2.

[0257] The results show that samples with a high Pt:Pd ratio in the Out-T coating layer have the same NO2 formation as samples containing W+Pt when HT aged.

[0258] Test results in Figure 12 The activity of the catalyst article (1) according to Example 7 and the reference catalyst according to Example 8 was investigated in a synthetic gas bench (SGB) in a light-off experiment, HT aged at 700° C. for 20 hours and SO aged at 400° C. for 20 hours. The results regarding the effect of tungsten and Pt:Pd ratio for the catalyst article (1) are shown in FIG.

[0259] According to this embodiment, the oxidation of NO to NO2 in the sample containing Pt+Pd in ​​the In-T coating layer and W+Pt in the Out-T coating layer (Example 7) was 10-18% higher than the oxidation of NO to NO2 in the sample containing Pt+Pd in ​​both the In-T and Out-T coating layers (Example 8) at 220-360°C.

[0260] The results show that using W+Pt in the Out-T coating layer results in better sulfur resistance compared to the Pt+Pd sample (even with a high Pt:Pd ratio).

[0261] Test results in Figure 13 The activity of the catalyst article (1) according to Example 7 and the reference catalyst according to Example 8 was investigated in a synthesis gas bench (SGB) in light-off experiments, HT aged at 700° C. for 20 hours and / or SO aged at 400° C. for 20 hours. The results regarding the effect of tungsten and Pt:Pd ratio on the studied catalyst article (1) are shown in FIG.

[0262] According to this embodiment, the sample containing Pt+Pd in ​​the In-T coating layer and W+Pt in the Out-T coating layer (Example 7) had the same THC ignition temperature (T) as the sample containing Pt+Pd in ​​both the In-T and Out-T coating layers (Example 8) under standard diesel gas mixture. 50 ) was achieved.

[0263] The results clearly show that the same THC oxidation activity is obtained under the studied conditions whether W+Pt or Pt+Pd is used in the Out-T coating layer.

[0264] Test results in Figure 14 The activity of the catalyst article (1) according to Example 9 and the reference catalyst according to Example 10 was investigated as HT700 aged in a synthetic gas bench (SGB) in a light-off experiment. The results regarding the effect of tungsten on the studied catalyst article (1) are shown in FIG.

[0265] According to this embodiment, the oxidation of NO to NO2 in the sample containing W+Pt in the Out-T coating layer (Example 9) was 8-12% higher than the oxidation of NO to NO2 in the sample containing only Pt in the Out-T coating layer (Example 10) at 230-380°C.

[0266] The results show that W promotes NO2 formation in the studied samples.

[0267] Test results in Figure 15 The activity of the catalyst article (1) according to Example 9 and the reference catalyst according to Example 10 was investigated as HT700 aged in a synthetic gas bench (SGB) in a light-off experiment. The results regarding the effect of tungsten on the studied catalyst article (1) are shown in FIG.

[0268] According to this embodiment, the sample containing Pt+Pd in ​​the In-T coating layer and W+Pt in the Out-T coating layer (Example 9) has the same THC ignition temperature (T) as the sample containing only Pt in the Out-T coating layer (Example 10) under standard diesel gas mixture. 50 ) and reached a CO ignition temperature 4°C higher than that.

[0269] The results show that W has a much smaller effect on the CO and THC oxidation activity relative to the sample containing Pt in the Out-T coating layer (without Pd).

[0270] Test results in Figure 16 and Table 2 - NO x Adsorption and desorption capacity The activity of the two-layer catalyst composition according to Examples 11a-g was measured using NO x The catalysts were investigated as new on a synthetic gas bench (SGB) in adsorption-desorption experiments. These catalyst compositions mimicked the various inlet and outlet compositions in the catalyst article (1). x The adsorption step was preceded by treatment at dilute conditions at 500 °C. x The adsorption capacities are shown in the following table according to the results of the desorption phase.

[0271] Using this embodiment, NO x The adsorption capacity is NO in the bottom layer. xThe adsorption capacity is increased significantly by adding adsorbents (Ce, ZrCe, La; or Pd-zeolite with or without Pt) (Table 2). The increase was also achieved when the top layer contained only PGM, Al oxide and occasionally W, but the adsorption capacity was calculated by the total weight of the bottom and top layers. With only alumina as support, the adsorption capacity was 9 μmol (without Pt) or 19 μmol / g of coating material.

[0272] The results showed that the presence of Pt in the Ce layer reduced the NO x The adsorption capacity was shown to be promoted by the in situ formation of NO2 at low concentrations at Pt sites near the Ce adsorbent in the bottom layer. The addition of Ce1 to the bottom layer with or without Pt / Pt+Pd increased the adsorption capacity to 37–58 μmol / g (2–5 times higher) even when only the bottom layer acted as the main adsorption layer.

[0273] When Zr-stabilized Ce oxide (ZrCe) was used, 33–50 μmol NO x / g, and 19 μmol NO x The adsorption capacity was measured using a coating of NO 3 / g. The Pt-only coating was intended for the outlet compartment, and the Pt+Pd coating was intended for the inlet compartment. x While this can be maximized by using only an adsorbent, the objective of this disclosure is to maximize the oxidation reaction during standard use or DPF regeneration, as well as the passive NO x The aim was to optimise the catalyst article (1) for adsorption-desorption.

[0274] All components (PGM, NO x The presence of the adsorbent (W) results in lower thermal / sulfur durability, lower Pt stabilization, lower NO due to component interactions and undesirable mass transfer limitations. x This can cause negative effects such as reduced adsorption capacity.

[0275] The results are applicable to typical lean applications involving exhaust gases from diesel, NG, or / and hydrogen fuel internal combustion. These compositions produce NO during the temperature increase up to about 180-250°C. x Some passive NO release x It acts as an adsorbent. [Table 2]

[0276] Based on the desorption results at 120–500 °C, the adsorption capacity was low even for porous alumina, which is typical of conventional DOCs, but the NO x was more tightly bound to the surface (Table 2, Figure 16). x Desorption was low below 200 °C (11% desorbed), which is due to downstream deNO x In contrast, catalysts containing cerium (Ce1), lanthanum and Pd-Fer can reduce the amount of adsorbed NO up to 200 °C. x released 36-43% of the

[0277] The sample containing Pd-Fer had a lower NO x Even if the catalyst had an alumina-based catalyst with almost the same adsorption capacity as NO x The release rate of NO was high (36%) up to 200 °C. The catalyst containing ZrCe+La released very well, but La nitrate was more stable than the nitrate on cerium oxide, with moderate adsorption strength and NO at higher temperatures. x It caused dislodging.

[0278] La and Ce oxides are more easily converted to nitrates (NO x ), but the capacity was three times higher than NO x The buffering effect of preventing NO emissions was much higher than that of alumina. x If emission buffering is required at higher temperatures, it can be combined with cerium materials. x High surface area (>200m) as an adsorbent 2 / g) Ce2 is NO x The adsorption capacity was significantly increased from 88 to 108 μmol / g.

[0279] In addition, NO x The release of NO was also very high at 49-59% below 200°C when using samples 11h and 11i. x The major portion (>50%) of NO2 is NO2, which has a promoting effect on NH3-SCR, HC-SCR and HC oxidation reactions at these low temperatures. x It is also possible for NO2 to be formed in the exhaust stream by desorption from the adsorbent at lower temperatures than the Pt-rich top layer or conventional DOC. x This is the benefit of adsorption-desorption. x These properties of passively adsorbing NO and oxidizing HC, CO and NO emissions effectively provide an integrated solution with desirable properties in a layered catalyst article (1).

[0280] This type of catalyst article (1) is useful for SCR catalysts, particularly for cold operating conditions, such as the World Harmonized Transient Cycle (WHTC), where the temperature is primarily below 200° C. for the first 400 seconds. x The use of adsorption-desorption can be evaluated by an example using a 4.4 L diesel engine, where raw NO x Total emissions for the cycle were approximately 50 grams (4.7g / kWh). x The adsorption-desorption is carried out by placing an efficient SCR catalyst (e.g., Cu-zeolite based) behind the catalytic article (1) to adsorb the desorbed NO x is used in all systems where reduction occurs at SCR operating temperatures.

[0281] As an example, 3.4dm 3 volume, 140 g / L coating amount, and approximately 100 μmol NO x When using catalyst article (1) (according to Examples 11h and 11i) having a coating total adsorption capacity of 1.0 g NO2 / g, the total adsorption capacity becomes about 2.2 g NO2 (at 120°C).

[0282] Therefore, the catalyst article (1) has a temperature cycle in the range of 50 to 250° C. and is capable of suppressing NO x If the adsorption capacity can be applied to the adsorption-desorption cycle 1-3 times, it can be roughly estimated that it has the potential to remove about 1-3 grams of NO2 during the first 500 seconds. x This potential of the catalyst article (1) to remove is significant when the auxiliary SCR system is in a cooling phase below 180° C. and the urea / NH3-SCR has not yet been activated.

[0283] NO over the cycle x In cold WHTC, where conversion is often less than 90%, the catalyst article (1) x This provides an opportunity to increase conversion efficiency by 2-6%, which is x This brings about a crucial improvement in removal efficiency.

[0284] Test results in Table 3 The activity of the catalyst article (1) according to Examples 12a-d was evaluated using NO x The new catalyst was investigated in adsorption-desorption experiments on a synthetic gas bench (SGB). The results of these experiments using a four-layer catalyst article (1) can be seen in Table 3. Ce2 has a small particle size and high NO x High surface area CeO with adsorption capacity x When both the inlet and outlet layers contained Ce2, the highest NO x The adsorption capacity was reached (Example 12a). x The amount of NO was also high in the temperature range of 120 to 200 °C. Even when Pd-Fer was used as the bottom layer at the inlet part and Pt + Pd + Al was used as the top layer (Example 12c), high NO x The adsorption capacity was shown. x The control (Example 12d) that does not contain an adsorbent compound exhibits lower NO x Adsorption capacity and relatively lower NO at 120-200°C x The combination of four layers in the catalyst article (1) clearly demonstrated the enhanced emission.

[0285] The absolute NO of the catalyst article (1) of the present disclosure at 120 to 200° C. x Desorption was 5-8 times higher than with the alumina-based reference. Pd-zeolites were more efficient than cerium compounds or other NO x NO than adsorbents x Although the adsorption capacity was low, NO x The release capacity was better. Pd-zeolite also x In addition to adsorption, it has a role in storing and oxidizing HCs to reduce their emissions during normal operation at low temperatures (<200° C.) or during DPF regeneration.

[0286] In this example, NO x NO for the total coating amount, including layers that do not contain adsorbent material x When calculating the adsorption capacity, NO x NO in the adsorbent layer x The adsorption capacity can be estimated to be about 100-150 μmol / g for Ce2. Therefore, NO x Depending on the amount of coating of the adsorbent-containing layer, NO x It is possible to adjust the adsorption capacity. NO x If adsorption capacity is required, a relatively higher PGM loading in the top or bottom layer can be used to further promote the reaction of NO to NO2 on the catalyst surface. [Table 3]

[0287] Test results in Figure 17 Corresponding to the previous test diagrams, the activity of the same catalyst articles (1) according to Examples 12a, 12b and 12d was investigated as new in a synthetic gas bench (SGB) in ignition experiments. The effect of these combinations on NO2 formation is shown in Figure 17.

[0288] According to this embodiment, NO x Contains adsorbent material and NOx All samples with different positions of the adsorbent material could achieve the same NO to NO2 oxidation activity. In addition to these tests, Examples 12a, 12b and 12d were studied as HT700 aged under regeneration conditions, where the THC light-off temperatures of these examples were found to be small (within 5°C). The results confirm that the Ce compound in the bottom layer has a small effect on NO2 formation and THC conversion on the catalyst article (1).

[0289] The best mode according to the present disclosure is given by the examples in which the inlet / outlet of the catalyst article (1) is given by examples 12a-c. In these combinations, the following features are used: - Layered structures with optimized PGM utilization and coating compositions; - Tungsten in the outlet distal layer to promote NO2 formation and increase stability against sulfur poisoning; - NO in the bottom layer x Adsorption-desorption characteristics of cold start DeNO x Enhance functionality, - NO in the inlet and outlet bottom (proximal) coating layers x High adsorption-desorption properties, NO x Achieve adsorption and desorption to achieve cold start deNO x Overall NO in the unit x While promoting removal, high NO2 formation and efficient HC oxidation are ensured during DPF regeneration conditions.

[0290] The main step of the present invention is to achieve high NOx emission by combining the layered structure design with tungsten dotting on the top layer of the outlet and NSC material on the bottom layer. x It is a step to combine adsorption-desorption and high NO2 formation with high thermal durability and sulfur resistance. By combining these examples with the optimization of PGM loading and Pt:Pd ratio in the coating layer, high efficiency of DPF activity regeneration at high HC concentration was also achieved.

[0291] Concluding remarks Although the invention has been described in detail for purposes of illustration, it will be understood that such detail is for purposes only and that variations can be made in the practice of the claimed subject matter by those skilled in the art from a study of the drawings, the disclosure, and the appended claims.

[0292] Where used in the claims, the term "comprising" does not exclude other elements or steps. Where used in the claims, the indefinite article "a" or "an" does not exclude a plurality. A single processor or other unit may fulfill several functions recited in the claims. Any reference signs used in the claims shall not be construed as limiting the scope.

Claims

1. A catalytic article (1) for purifying an exhaust gas at lean exhaust gas conditions, said catalytic article (1) comprising flow paths (3) allowing an exhaust gas to traverse said catalytic article (1), thereby defining inlets and outlets for said exhaust gas and a flow direction of a flow path for said exhaust gas traversing said catalytic article (1), said flow paths (3) providing a surface of a substrate (2) for carrying one or more catalytically active layers (11, 12, 21, 22) for converting at least a respective first and a respective second undesirable chemical component contained in said exhaust gas into at least a corresponding first or a corresponding second desired chemical component during the passage of said exhaust gas through said catalytic article (1), - at least a first and a second catalyst section (10, 20) are arranged on said substrate (2), each respective catalyst section (10, 20) comprising at least said respective first and said respective second catalyst layer (11, 12), (21, 22) arranged such that said respective first catalyst layer (11, 21) is proximal to said substrate (2) and said respective second catalyst layer (12, 22) is distal to said substrate (2); - each of said first and second catalyst layers (11, 12, 21, 22) is chemically different in pairs; - said first catalyst section (10) is arranged in said flow path (3) such that, during the traversal of said flow path (3), said exhaust gas first encounters said first catalyst section (10) and then encounters said second catalyst section (20); - said second catalytic section (20) promotes, and said first catalytic section (10) does not substantially promote, the catalytic conversion of either said respective first or second undesired chemical constituent into said corresponding first or second desired chemical constituent; The above catalyst article (1).

2. 2. The catalytic article (1) of claim 1, wherein at least a third section (30) is arranged in the flow path (3) after the first catalyst section (10) and before the second catalyst section (20) in the flow direction of the exhaust gas through the flow path (3).

3. The first catalyst section (10) is adapted to separate hydrocarbons, H 2 3. The catalytic article (1) of claim 1 or 2, wherein the first catalytic section (20) is selective for converting nitric oxide (NO) to nitrogen dioxide and / or carbon monoxide (CO) to water and carbon dioxide, and the second catalytic section (20) is selective for converting nitric oxide to nitrogen dioxide and / or sulfur dioxide to sulfur trioxide.

4. 4. The catalyst article (1) of claim 3, wherein the first catalyst section (10) comprises in the first proximal catalyst layer (11) one or more catalytically active metals selected from platinum group metals (PGMs) including Pt, Pd, Rh, Ir, Ru, Os at a metal loading of less than 0.8 g / L and in the first distal catalyst layer (12) one or more catalytically active metals selected from platinum group metals (PGMs) including Pt, Pd, Rh, Ir, Ru, Os at a metal loading of between 0.5 and 7.0 g / L, with the proviso that the metal loading in the first distal catalyst layer (12) is greater than the metal loading in the first proximal catalyst layer (11).

5. 5. The catalytic article (1) of claim 4, wherein the platinum group metal selected for the first proximal (11) and distal (12) catalytic layers is platinum and / or palladium.

6. 6. The catalytic article (1) of claim 5, wherein platinum and palladium are present in the first distal catalytic layer (12) in a Pt:Pd ratio ranging from 1:4 to 5:1 and in the first proximal catalytic layer (11) in a Pt:Pd ratio ranging from 1:9 to 9:

1.

7. 4. The catalyst article (1) of claim 3, wherein the second catalyst section (20) of the second proximal catalyst layer (21) comprises one or more catalytically active metals selected from platinum group metals (PGM) including Pt, Pd, Rh, Ir, Ru, Os at a metal loading of less than 0.8 g / L and the second catalyst section (20) of the second distal catalyst layer (22) comprises one or more catalytically active metals selected from platinum group metals (PGM) including Pt, Pd, Rh, Ir, Ru, Os at a metal loading of between 0.1 and 2.0 g / L, with the proviso that the metal loading in the second distal catalyst layer (22) is greater than the metal loading in the second proximal catalyst layer (21), and the second distal catalyst layer (22) further comprises tungsten (W) and / or molybdenum (Mo) in an amount sufficient to promote conversion of NOx to nitrogen dioxide.

8. 8. The catalytic article (1) of claim 7, wherein the platinum group metal selected for the second proximal (21) and distal (22) catalytic layers is platinum and / or palladium.

9. 9. The catalyst article (1) of claim 8, wherein the Pt:Pd ratio in the second distal catalyst layer (22) ranges from 1:0 to 30:1 and the Pt:Pd ratio in the second proximal catalyst layer (21) ranges from 1:9 to 9:

1.

10. Tungsten (W) is present in the second distal catalyst layer (22) in a range of 1 to 30 g / L of tungsten oxide (WO 3 10. The catalytic article (1) according to any one of claims 7 to 9, wherein the catalytic article (1) is present as a catalyst.

11. 11. The catalytic article (1) according to any one of claims 3 to 10, wherein the PGM loading in the catalytic layers (11, 12, 21, 22) follows the order In-T > Out-T > In-B > Out-B, but preferably In-T > Out-T > In-B > Out-B.

12. The first (11) and second (21) proximal catalyst layers are x NO by adsorption-desorption and desorption below 200°C 2 12. The catalytic article (1) of any one of claims 3 to 11, further comprising a sufficient amount of cerium (Ce) oxide or cerium mixed oxides selected from ZrCe, MnCe, TiCe, PrCe oxides or combinations thereof to promote the formation of a cerium oxide.

13. Catalyst article (1) according to claim 12, wherein the cerium in the form of cerium oxide or cerium mixed oxide is present in an amount of 0.05 g / L to 0.5 g / L based on the total weight of the cerium oxide or cerium mixed oxide.

14. The first (11) and second (21) proximal catalyst layers are provided with NO of the first and second proximal catalyst layers. x and S.O. x 14. The catalytic article (1) according to any one of claims 3 to 13, further comprising lanthanum (La), yttrium (Y), hafnium (Hf), or combinations thereof, but preferably lanthanum, as stable oxides in an amount ranging from 1 to 10 g / L, preferably 3 to 6 g / L, to promote adsorption capacity.

15. The first (11) and second (21) proximal catalyst layers are x To increase the adsorption capacity, a high Si / Al catalyst is selected from Beta, ZSM-5, Chabazite (CHA), AEI, Ferrierite (Fer), Y or a combination thereof in an amount of 5 to 1000 g / L, but preferably 10 to 50 g / L. 2 Catalyst article (1) according to any one of claims 3 to 14, further comprising one or more zeolites having a ratio (SAR).

16. The catalyst layers (11, 12, 21, 22) contain, in addition to the catalyst promoter, aluminum oxide, alumina (Al 2 O 3 ), silicon oxide (SiO x ), silica (SiO 2 ), titanium oxide (TiO x ), titania (TiO 2 16. The catalytic article (1) according to any one of claims 3 to 15, comprising a porous support selected from porous metal oxides including arsenic, ...

17. 17. The catalytic article (1) of claim 16, wherein the amount of coating in each coating layer is between 10 and 200 g / L, preferably between 40 and 100 g / L, more preferably between 50 and 80 g / L in all layers of the catalytic article (1), the porous metal oxide forming the remainder of the coating composition.